Radical-generating film-forming composition, radical-generating film, and method for producing in-plane switching liquid crystal cell
A radical generating membrane composition using polyimide precursors and diamines addresses the challenges of high transmittance and fast response speed in liquid crystal displays, improving image quality and production efficiency.
Patent Information
- Application Number
- JP2021565682
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-18
- Filing Date
- 2020-12-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-12-18
AI Technical Summary
Existing liquid crystal display elements face challenges in achieving high backlight transmittance, fast response speed, and stable polymer brush formation on substrates, which are crucial for mass production and controlling electrical properties, while also dealing with issues like unevenness, grilling, and slow response times.
A radical generating membrane formation composition containing specific polyimide precursors and diamines with organic groups that induce radical polymerization is used to form a stable, low-anchoring energy liquid crystal orientation film, enabling high transmittance and fast response speed.
The solution allows for a liquid crystal display element with improved backlight transmittance and response speed, reducing power consumption and enhancing image quality, while being suitable for mass production and cost-effective.
Smart Images

Figure 0007622647000043 
Figure 0007622647000044 
Figure 0007622647000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a radical-generating film-forming composition that can be suitably used in weak anchoring liquid crystal display elements and the like, and to a radical-generating film. The present invention also relates to a method for producing an in-plane switching liquid crystal cell using the radical-generating film-forming composition or the radical-generating film. [Background technology]
[0002] In recent years, liquid crystal display elements are widely used in displays for mobile phones, computers, and televisions. Liquid crystal display elements have characteristics such as thinness, light weight, and low power consumption, and are expected to be applied to further content in the future, such as VR (Virtual Reality) and ultra-high resolution displays. Various display modes have been proposed for liquid crystal displays, such as TN (Twisted Nematic), IPS (In-Plane Switching), and VA (Vertical Alignment), and all modes use a film (liquid crystal alignment film) that guides the liquid crystal into a desired alignment state.
[0003] In particular, for products equipped with touch panels such as tablet PCs, smartphones, and smart TVs, the IPS mode is preferred because it is less likely to distort the display when touched. In recent years, LCD display elements using FFS (Frindge Field Switching) and non-contact technology using optical alignment have come to be used to improve contrast and viewing angle characteristics.
[0004] In recent years, there has been a trend toward even higher resolution and contrast, such as 4K and 8K, and the brightness of backlights is also increasing. Accordingly, LCD elements are also being targeted for improvement in transmittance and lower drive voltage, and since the FFS mode in particular is used not only for TV applications but also for tablets, smartphones, etc., improving transmittance and reducing drive voltage are extremely important issues.
[0005] Regarding improving the transmittance of liquid crystal display elements, a method of using negative liquid crystal has been proposed for FFS mode, and is being put to practical use. On the other hand, when using negative liquid crystal, although it is very effective in improving transmittance, it also involves a deterioration in response time and an increase in driving voltage, so it is not very effective in reducing power consumption, and there are also problems with the negative liquid crystal itself being prone to dissolving contaminants, which can easily cause defects such as unevenness and burn-in.
[0006] Recently, weak anchoring IPS technology, which uses a film with very low anchoring energy as a liquid crystal alignment film, has been attracting attention as a technology that can improve the transmittance and reduce the driving voltage of liquid crystal display elements. Weak anchoring IPS technology can greatly improve the transmittance and reduce the driving voltage even when an IPS substrate with a relatively wide comb-tooth electrode width is used as the substrate, so if it can be put into practical use, it will have the advantage of being able to reduce the cost of the substrate and suppress the occurrence of flicker, which is a problem specific to the FFS mode (see Patent Document 1).
[0007] In recent years, a zero-plane anchoring IPS mode (also called weak anchoring IPS mode) technology has been proposed, in which a zero-plane anchoring state is created using dense polymer brushes, etc. (See Reference 2.) This technology has achieved a significant improvement in contrast ratio and a significant reduction in drive voltage. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 4053530 [Patent Document 2] JP 2013-231757 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, this technology has some problems that arise in principle. First, extremely delicate conditions are required to stably generate the polymer brushes on the substrate, which is not realistic for mass production. Second, the alignment film plays an important role in preventing image sticking, but when using polymer brushes, it is difficult to control the necessary electrical properties. Third, due to the driving principle, the response speed when the voltage is turned off is very slow. By making the alignment restraint force zero, the resistance applied to the liquid crystal during driving is eliminated, which is expected to significantly reduce the threshold voltage and improve brightness by reducing the areas of poor alignment during driving. However, as for the return of the liquid crystal, the force of the return of the liquid crystal depends on the elasticity of the liquid crystal, so it is thought that the speed will be significantly slower than when an alignment film is present.
[0010] If these technical challenges can be resolved, it will bring significant cost benefits to panel manufacturers, and it is also expected that this will result in benefits such as reduced battery consumption and improved image quality.
[0011] The present invention has been made to solve the above-mentioned problems, and aims to provide a horizontal electric field liquid crystal display element that can simultaneously achieve non-contact alignment, low driving voltage, and fast response speed when the voltage is off at room temperature in a simple and inexpensive manner by applying polymer stabilization technology that can produce a weak anchoring film. In particular, it is an object of the present invention to provide an in-plane switching liquid crystal display element capable of providing a good black display, high backlight transmittance, and fast response speed. In order to obtain such an excellent in-plane switching liquid crystal display element, the present invention has an object to provide a radical-generating film-forming composition for use in the in-plane switching liquid crystal display element. [Means for solving the problem]
[0012] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved, and have completed the present invention having the following gist.
[0013] That is, the present invention includes the following. [1] A polymer having a structural unit represented by the following formula (1) in its main chain as component (A), and A polymer used as an alignment component of a liquid crystal alignment agent for in-plane switching drive, which is the component (B); A radical-generating film-forming composition comprising: [ka] (In formula (1), A represents an organic group that induces radical polymerization.) [2] The radical-generating film-forming composition according to [1], wherein the polymer of component (A) is at least one polymer selected from a polyimide precursor, a polyimide, a polyurea, and a polyamide obtained using a diamine component containing a diamine containing an organic group that induces radical polymerization.
[0014] [3] The radical-generating film-forming composition according to [2], wherein the diamine containing an organic group capable of inducing radical polymerization is a diamine represented by the following formula (2): [ka] (In formula (2), A 1 and A 2 Each represents a hydrogen atom or an organic group that induces radical polymerization, where A 1 and A 2 At least one of represents an organic group capable of inducing radical polymerization, E is a single bond, -O-, -C(CH3)2-, -NH-, -CO-, -NHCO-, -COO-, -(CH2) m represents a divalent organic group consisting of -, -SO2-, or any combination thereof, and m represents an integer of 1 to 8.
[0015] p represents an integer from 0 to 2. When p is 2, multiple A 2 Each independently has the same definition as above. When p is 0, A 1 consists of organic groups that induce radical polymerization. [4] The radical-generating film-forming composition according to any one of [1] to [3], wherein the organic group capable of inducing radical polymerization is a group represented by the following formula (3): [ka] (In formula (3), the dashed line represents a bond to a benzene ring, and R 6 represents a single bond, -CH2-, -O-, -COO-, -OCO-, -NHCO-, -CONH-, -NH-, -CHO-, -N(CH3)-, -CON(CH3)-, or -N(CH3)CO-, R 7 represents a single bond, or an alkylene group having 1 to 20 carbon atoms which is unsubstituted or substituted with a fluorine atom, and one or more of any -CH2- or -CF2- in the alkylene group may be independently replaced with a group selected from -CH=CH-, a divalent carbocycle, and a divalent heterocycle, and may further be replaced with any of the following groups, i.e., -O-, -COO-, -OCO-, -NHCO-, -CONH-, or -NH-, provided that they are not adjacent to each other.
[0016] R 8 represents an organic group capable of inducing radical polymerization, represented by a formula selected from the formulae [X-1] to [X-18], [W], [Y], and [Z]; [ka] In formulas [X-1] to [X-18], * represents R 7 each of S1 and S2 independently represents -O-, -NR-, or -S-; R represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; each of R1 and R2 independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 4 carbon atoms;
[0017] [ka] In the formula [W], [Y], and [Z], * is R 7 represents the bond with S3 represents a single bond, -O-, -S-, -COO-, -OCO-, -NHCO-, -CONH-, -NH-, -CHO-, -N(CH)-, -CON(CH)-, or -N(CH)CO-; Ar represents an aromatic hydrocarbon group selected from the group consisting of phenylene, naphthylene, and biphenylylene, which may have an organic group and / or a halogen atom as a substituent; R 9 and R 10 are each independently an alkyl group, an alkoxy group, a benzyl group, or a phenethyl group having 1 to 10 carbon atoms. In the case of an alkyl group or an alkoxy group, R 9 and R 10 may form a ring,
[0018] Q represents one of the following structures: [ka] In the formula, R 11 represents -CH2-, -NR-, -O-, or -S-, R represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, * represents a bond, R 12 represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms.
[0019] [5] A radical-generating film obtained by using the radical-generating film-forming composition according to any one of [1] to [4]. [6] preparing a first substrate having a liquid crystal alignment film and a second substrate having the radical generating film described in [5]; preparing a cell such that a radical generating film on the second substrate faces the first substrate; and A method for manufacturing a horizontal electric field liquid crystal cell, comprising a step of filling a liquid crystal composition containing liquid crystal and a radically polymerizable compound between the first substrate and the second substrate, wherein one of the first substrate and the second substrate is a comb electrode substrate and the other is an opposing substrate. [7] The method for producing an in-plane switching liquid crystal cell according to [6], wherein the first substrate is a substrate coated with a liquid crystal alignment film having uniaxial alignment properties. [8] The method for producing a lateral electric field liquid crystal cell according to [7], wherein the liquid crystal alignment film having uniaxial alignment is a liquid crystal alignment film for horizontal alignment. [9] The method for producing a lateral electric field liquid crystal cell according to any one of [6] to [8], wherein the comb electrode substrate is an IPS substrate or an FFS substrate. Effect of the Invention
[0020] According to the present invention, in order to obtain an in-plane switching liquid crystal display element capable of providing a good black display and realizing a high backlight transmittance and a fast response speed, it is possible to provide a radical-generating film-forming composition that can be effectively used in the in-plane switching liquid crystal display element. [Brief description of the drawings]
[0021] [Figure 1] 1 is a schematic cross-sectional view showing an example of a liquid crystal display element according to the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing another example of a liquid crystal display element according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] (Radical-generating film-forming composition) The radical-generating film-forming composition of the present invention contains the component (A) and the component (B).
[0023] <Component (A)> The present invention contains, as component (A), a polymer having a structural unit represented by the above formula (1) in the main chain. As a result, the radical-generating film-forming composition of the present invention contains an organic group that induces radical polymerization. By applying and curing such a composition to form a film, the group capable of generating radicals is fixed in the film, and a liquid crystal alignment film having various functions can be obtained.
[0024] Such an organic group capable of inducing radical polymerization includes the group represented by the above formula (3).
[0025] Specifically, the organic group represented by the formula selected from the above [W], [Y] and [Z] is preferably the following: In particular, (b) and (c) are preferred from the viewpoint of the reliability of the resulting liquid crystal display device. [ka]
[0026] When using the polymer having an organic group that induces radical polymerization as the component (A) used in the present invention, in order to obtain a polymer having a group that can generate radicals, it is preferable to produce the polymer using, as a monomer component, a monomer having a photoreactive side chain containing at least one selected from a methacryl group, an acrylic group, a vinyl group, an allyl group, a coumarin group, a styryl group, and a cinnamoyl group, or a monomer having a site in a side chain that decomposes and generates radicals by ultraviolet irradiation. On the other hand, since the monomer that generates radicals may have problems such as spontaneously polymerizing itself and becomes an unstable compound, from the viewpoint of ease of synthesis, a polymer derived from a diamine having a radical generating site is preferable, and polyimide precursors such as polyamic acid and polyamic acid ester, polyimide, polyurea, polyamide, etc. are more preferable.
[0027] Specific examples of such diamines containing a radical generating site include diamines having a side chain capable of generating radicals and polymerizing, such as diamines represented by the above formula (2), but are not limited thereto. In the above formula (2), E is a single bond, -O-, -C(CH3)2-, -NH-, -CO-, -NHCO-, -COO-, -(CH2) m represents a divalent organic group consisting of -, -SO2-, or any combination thereof, and here, "any combination thereof" includes -O-(CH2) m -O-, -OC(CH3)2-, -CO-(CH2) m -, -NH-(CH2) m -, -SO2-(CH2) m -, -CONH-(CH2) m -, -CONH-(CH2) m-NHCO-, -COO-(CH2) m Examples include, but are not limited to, -OCO-.
[0028] The bonding positions of the two amino groups (-NH2) in the radical generating site-containing diamine (specifically, for example, formula (2)) are not limited. Specific examples include the 2,3 position, the 2,4 position, the 2,5 position, the 2,6 position, the 3,4 position, and the 3,5 position on the benzene ring relative to the bonding group of the side chain. Among these, from the viewpoint of reactivity in synthesizing a polyamic acid, the 2,4 position, the 2,5 position, or the 3,5 position is preferred. Taking into account the ease of synthesizing a diamine, the 2,4 position or the 3,5 position is more preferred.
[0029] Specific examples of diamines having a photoreactive group containing at least one selected from the group consisting of a methacryl group, an acrylic group, a vinyl group, an allyl group, a coumarin group, a styryl group, and a cinnamoyl group include, but are not limited to, the following compounds. [ka]
[0030] [ka] (In the formula, J 1 represents a single bond, -O-, -COO-, -NHCO-, or -NH-; J 2 represents a single bond, or an unsubstituted or fluorine-substituted alkylene group having 1 to 20 carbon atoms.
[0031] As the diamine having an organic group represented by the formula selected from the above [W], [Y], and [Z], in consideration of ease of synthesis, high versatility, properties, etc., the structure represented by the following formula is most preferable, but is not limited to this. [ka] (In the formula, n is an integer of 2 to 8, and E is a single bond, -O-, -C(CH3)2-, -NH-, -CO-, -NHCO-, -COO-, -(CH2) m -, -SO2-, -O-(CH2) m -O-, -OC(CH3)2-, -CO-(CH2) m -, -NH-(CH2) m -, -SO2-(CH2) m -, -CONH-(CH2) m -, -CONH-(CH2) m -NHCO- or -COO-(CH2) m -OCO-, and m is an integer of 1 to 8.
[0032] [ka] (In the formula, n is an integer of 2 to 8.)
[0033] The above diamines can be used alone or in combination of two or more depending on the properties such as liquid crystal alignment properties, sensitivity in the polymerization reaction, voltage retention properties, and stored charge when formed into a radical generating film.
[0034] The diamine having such a site where radical polymerization occurs is preferably used in an amount of 5 to 100 mol %, more preferably 10 to 80 mol %, and particularly preferably 30 to 50 mol %, of the total diamine components used in the synthesis of the polymer, which is component (A) contained in the radical-generating film-forming composition.
[0035] When the polymer (A) used in the radical-generating film-forming composition of the present invention is obtained from a diamine, other diamines than the diamines having the radical-generating sites can be used as the diamine components. Specifically, p-phenylenediamine, 2,3,5,6-tetramethyl-p-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, m-phenylenediamine, 2,4-dimethyl-m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 2,5-diaminophenol, 2,4-diaminophenol, 3,5-diaminophenol, 3,5-diaminobenzyl alcohol, 2,4-diaminobenzyl alcohol, 4,6-diaminoresorcinol, 4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 3,3'-dicarboxy-4,4'-diaminobiphenyl, 3,3'-difluoro-4,4'-diaminobiphenyl, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,4'-diaminobiphenyl, 3,3'-diaminobiphenyl, 2,2'-diaminobiphenyl Phenyl, 2,3'-diaminobiphenyl, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2'-diaminodiphenylmethane, 2,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylether, 3,3'-diaminodiphenylether, 3,4'-diaminodiphenylether, 2,2'-diaminodiphenylether, 2,3'-diaminodiphenylether, 4,4'-sulfonyldianiline , 3,3'-sulfonyldianiline, bis(4-aminophenyl)silane, bis(3-aminophenyl)silane, dimethyl-bis(4-aminophenyl)silane, dimethyl-bis(3-aminophenyl)silane, 4,4'-thiodianiline, 3,3'-thiodianiline, 4,4'-diaminodiphenylamine, 3,3'-diaminodiphenylamine, 3,4'-diaminodiphenylamine, 2,2'-diaminodiphenylamine, 2,3'-diaminodiphenylamine, N-methyl(4,4'-diaminodiphenyl)amine, N-methyl(3,3'-diaminodiphenyl)amine, N-methyl(3,4'-diaminodiphenyl)amine, N-methyl(2,2'-diaminodiphenyl)amine, N-methyl(2,3'-diaminodiphenyl)amine, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 3,4'-diaminobenzophenone, 2,2'-diaminobenzophenone, 2,3'-diaminobenzophenone, 1,4-diaminonaphthalene, 1,5-diaminonaphthalene, 1,6-diaminonaphthalene, 1,7-diaminonaphthalene, 1,8-diaminonaphthalene, 2,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,7-diaminonaphthalene, 1,2-bis(4-aminophenyl)ethane, 1,2-bis(3-aminophenyl)ethane, 1,3-bis(4-aminophenyl)propane, 1,3-bis(3-aminophenyl)propane, 1,4-bis(4-aminophenyl)butane, 1,4-bis(3-aminophenyl)butane, bis(3,5-diethyl-4-aminophenyl)methane, 1,4-bis(4-aminophenoxy)benzene Zene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(4-aminobenzyl)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-[1,4-phenylenebis(methylene)]dianiline, 4,4'-[1,3-phenylenebis(methylene)]dianiline, 3,4'-[1,4-phenylenebis(methylene)]dianiline, 3,4'-[1,3-phenylenebis(methylene)]dianiline, 3,3'-[1,4 -phenylenebis(methylene)]dianiline, 3,3'-[1,3-phenylenebis(methylene)]dianiline, 1,4-phenylenebis[(4-aminophenyl)methanone], 1,4-phenylenebis[(3-aminophenyl)methanone], 1,3-phenylenebis[(4-aminophenyl)methanone], 1,3-phenylenebis[(3-aminophenyl)methanone], 1,4-phenylenebis(4-aminobenzoate), 1,4-phenylenebis(3-aminobenzoate), 1,3-phenylenebis(4-aminobenzoate), 1,3-phenylenebis(3-aminobenzoate), bis(4-aminophenyl)terephthalate, bis(3-aminophenyl)terephthalate, bis(4-aminophenyl)isophthalate, bis(3-aminophenyl)isophthalate, N,N'-(1,4-phenylene)bis(4-aminobenzamide), N,N'-(1,3-phenylene)bis(4-aminobenzamide), N,N'-(1,4-phenylene)bis(3-aminobenzamide), N,N'-(1,3-phenylene)bis(3-aminobenzamide), N,N'-bis(4-amino N,N'-bis(3-aminophenyl)terephthalamide, N,N'-bis(4-aminophenyl)isophthalamide, N,N'-bis(3-aminophenyl)isophthalamide, 9,10-bis(4-aminophenyl)anthracene, 4,4'-bis(4-aminophenoxy)diphenylsulfone, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(4-aminophenyl)hexafluoropropane propane, 2,2'-bis(3-aminophenyl)hexafluoropropane, 2,2'-bis(3-amino-4-methylphenyl)hexafluoropropane, 2,2'-bis(4-aminophenyl)propane, 2,2'-bis(3-aminophenyl)propane, 2,2'-bis(3-amino-4-methylphenyl)propane, trans-1,4-bis(4-aminophenyl)cyclohexane, 3,5-diaminobenzoic acid, 2,5-diaminobenzoic acid, bis(4-aminophenoxy)methane, 1,2-bis(4-aminophenoxy)ethane, 1,3-bis (4-aminophenoxy)propane, 1,3-bis(3-aminophenoxy)propane, 1,4-bis(4-aminophenoxy)butane, 1,4-bis(3-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)pentane, 1,5-bis(3-aminophenoxy)pentane, 1,6-bis(4-aminophenoxy)hexane, 1,6-bis(3-aminophenoxy)hexane, 1,7-bis(4-aminophenoxy)heptane, 1,7-bis(3-aminophenoxy)heptane, 1,8-bis(4-aminophenoxy)octane, 1,Aromatic diamines such as 8-bis(3-aminophenoxy)octane, 1,9-bis(4-aminophenoxy)nonane, 1,9-bis(3-aminophenoxy)nonane, 1,10-bis(4-aminophenoxy)decane, 1,10-bis(3-aminophenoxy)decane, 1,11-bis(4-aminophenoxy)undecane, 1,11-bis(3-aminophenoxy)undecane, 1,12-bis(4-aminophenoxy)dodecane, and 1,12-bis(3-aminophenoxy)dodecane; alicyclic diamines such as bis(4-aminocyclohexyl)methane and bis(4-amino-3-methylcyclohexyl)methane; 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, and 1,7-diaminoheptane. aliphatic diamines such as 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, 1,11-diaminoundecane, and 1,12-diaminododecane; diamines having a urea structure such as 1,3-bis[2-(p-aminophenyl)ethyl]urea and 1,3-bis[2-(p-aminophenyl)ethyl]-1-tert-butoxycarbonylurea; diamines having a nitrogen-containing unsaturated heterocyclic structure such as Np-aminophenyl-4-p-aminophenyl(tert-butoxycarbonyl)aminomethylpiperidine; and diamines having an N-Boc group (Boc represents a tert-butoxycarbonyl group) such as N-tert-butoxycarbonyl-N-(2-(4-aminophenyl)ethyl)-N-(4-aminobenzyl)amine.
[0036] The above other diamines can be used alone or in combination of two or more depending on the properties such as liquid crystal alignment properties, sensitivity in the polymerization reaction, voltage retention properties, and stored charge when formed into a radical generating film.
[0037] In the synthesis of a polymer in the form of a polyamic acid, the tetracarboxylic dianhydride to be reacted with the diamine component is not particularly limited. Specifically, pyromellitic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 1,2,5,6-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 2,3,6,7-anthracenetetracarboxylic acid, 1,2,5,6-anthracenetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, bis(3,4-dicarboxyphenyl)ether, 3,3',4,4'-benzophenonetetracarboxylic acid, bis(3,4-dicarboxyphenyl)ether ... 2,2-bis(3,4-dicarboxyphenyl)sulfone, bis(3,4-dicarboxyphenyl)methane, 2,2-bis(3,4-dicarboxyphenyl)propane, 1,1,1,3,3,3-hexafluoro-2,2-bis(3,4-dicarboxyphenyl)propane, bis(3,4-dicarboxyphenyl)dimethylsilane, bis(3,4-dicarboxyphenyl)diphenylsilane, 2,3,4,5-pyridinetetracarboxylic acid, 2,6-bis(3,4-dicarboxyphenyl)pyridine, 3,3',4,4'-diphenylsulfone Tetracarboxylic acids, 3,4,9,10-perylenetetracarboxylic acid, 1,3-diphenyl-1,2,3,4-cyclobutanetetracarboxylic acid, oxydiphthaltetracarboxylic acid, 1,2,3,4-cyclobutanetetracarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic acid, 1,2-dimethyl-1,2,3,4-cyclobutanetetracarboxylic acid, 1,3-dimethyl-1 ,2,3,4-cyclobutanetetracarboxylic acid, 1,2,3,4-cycloheptanetetracarboxylic acid, 2,3,4,5-tetrahydrofurantetracarboxylic acid, 3,4-dicarboxy-1-cyclohexylsuccinic acid, 2,3,5-tricarboxycyclopentylacetic acid, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalenesuccinic acid, bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic acid, bicyclo[4.3.0]nonane-2,4,7,9-tetracarboxylic acid, bicyclo[4.4.0]decane-2,4,7,9-tetracarboxylic acid, bicyclo[4.4.0]decane-2,4,8,10-tetracarboxylic acid, tricyclo[6.3.0.0<2,6>]undecane-3,5,9,11-tetracarboxylic acid, 1,2,3,4-butanetetracarboxylic acid, 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydrinaphthalene-1,2-dicarboxylic acid, bicyclo[2.2.2]oct-7-ene Examples of dianhydrides of tetracarboxylic acids include norbornane-2,3,5,6-tetracarboxylic acid, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexane-1,2-dicarboxylic acid, tetracyclo[6.2.1.1<3,6>.0<2,7>]dodeca-4,5,9,10-tetracarboxylic acid, 3,5,6-tricarboxynorbornane-2:3,5:6 dicarboxylic acid, and 1,2,4,5-cyclohexanetetracarboxylic acid.
[0038] Of course, one or more kinds of tetracarboxylic dianhydrides may be used in combination depending on the properties such as liquid crystal alignment properties, sensitivity in polymerization reaction, voltage retention properties, and accumulated charge when used as a radical generating film.
[0039] In the synthesis of a polyamic acid ester polymer, the structure of the tetracarboxylic acid dialkyl ester reacted with the above diamine component is not particularly limited, but specific examples are given below.
[0040] Specific examples of the aliphatic tetracarboxylic acid diester include 1,2,3,4-cyclobutane tetracarboxylic acid dialkyl ester, 1,2-dimethyl-1,2,3,4-cyclobutane tetracarboxylic acid dialkyl ester, 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic acid dialkyl ester, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutane tetracarboxylic acid dialkyl ester, 1,2,3,4-cyclopentane tetracarboxylic acid dialkyl ester, 2,3,4,5-tetrahydrofuran tetracarboxylic acid dialkyl ester, 1,2,4,5-cyclohexane tetracarboxylic acid dialkyl ester, 3,4-dicarboxy-1-cyclohexyl succinic acid dialkyl ester, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic acid dialkyl ester, 1,2,3,4-butane tetracarboxylic acid dialkyl ester, esters, bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic acid dialkyl esters, 3,3',4,4'-dicyclohexyl tetracarboxylic acid dialkyl esters, 2,3,5-tricarboxycyclopentyl acetate dialkyl esters, cis-3,7-dibutylcycloocta-1,5-diene-1,2,5,6-tetracarboxylic acid dialkyl esters, tricyclo[4.2.1.0<2,5>]nonane-3,4, Examples of such alkyl esters include 7,8-tetracarboxylic acid-3,4:7,8-dialkyl esters, hexacyclo[6.6.0.1<2,7>.0<3,6>.1<9,14>.0<10,13>]hexadecane-4,5,11,12-tetracarboxylic acid-4,5:11,12-dialkyl esters, and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic acid dialkyl esters.
[0041] Examples of aromatic tetracarboxylic acid dialkyl esters include pyromellitic acid dialkyl esters, 3,3',4,4'-biphenyl tetracarboxylic acid dialkyl esters, 2,2',3,3'-biphenyl tetracarboxylic acid dialkyl esters, 2,3,3',4-biphenyl tetracarboxylic acid dialkyl esters, 3,3',4,4'-benzophenone tetracarboxylic acid dialkyl esters, 2,3,3',4'-benzophenone tetracarboxylic acid dialkyl esters, bis(3,4-dicarboxyphenyl)ether dialkyl esters, bis(3,4-dicarboxyphenyl)sulfone dialkyl esters, 1,2,5,6-naphthalene tetracarboxylic acid dialkyl esters, and 2,3,6,7-naphthalene tetracarboxylic acid dialkyl esters.
[0042] In the synthesis of a polyurea polymer, the diisocyanate to be reacted with the diamine component is not particularly limited, and can be used depending on availability, etc. Specific structures of diisocyanates are shown below. [ka] R in the formula 22 and R 23 represents an aliphatic hydrocarbon group having 1 to 10 carbon atoms.
[0043] Aliphatic diisocyanates shown in K-1 to K-5 have the advantage of being inferior in reactivity but improving solvent solubility, while aromatic diisocyanates shown in K-6 to K-7 are highly reactive and have the effect of improving heat resistance, but have the disadvantage of reducing solvent solubility. In terms of versatility and properties, K-1, K-7, K-8, K-9, and K-10 are preferred, while K-12 is preferred from the viewpoint of electrical properties, and K-13 is preferred from the viewpoint of liquid crystal alignment. Diisocyanates can be used in combination of one or more types, and it is preferable to apply them in various ways depending on the properties you want to obtain.
[0044] In addition, a part of the diisocyanate may be replaced with the above-described tetracarboxylic dianhydride, and the polyimide may be used in the form of a copolymer of polyamic acid and polyurea, or may be used in the form of a copolymer of polyimide and polyurea by chemical imidization.
[0045] In the synthesis of a polyamide polymer, the structure of the dicarboxylic acid to be reacted is not particularly limited, but specific examples are as follows: Specific examples of aliphatic dicarboxylic acids include dicarboxylic acids such as malonic acid, oxalic acid, dimethylmalonic acid, succinic acid, fumaric acid, glutaric acid, adipic acid, muconic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, 3,3-diethylsuccinic acid, azelaic acid, sebacic acid, and suberic acid.
[0046] Examples of alicyclic dicarboxylic acids include 1,1-cyclopropanedicarboxylic acid, 1,2-cyclopropanedicarboxylic acid, 1,1-cyclobutanedicarboxylic acid, 1,2-cyclobutanedicarboxylic acid, 1,3-cyclobutanedicarboxylic acid, 3,4-diphenyl-1,2-cyclobutanedicarboxylic acid, 2,4-diphenyl-1,3-cyclobutanedicarboxylic acid, 1-cyclobutene-1,2-dicarboxylic acid, 1-cyclobutene-3,4-dicarboxylic acid, 1,1-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,1-cyclohexanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,1-cyclohexanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,1-cyclohexanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,1-cyclohexanedicarboxylic acid, 1,2-cyclopentane ...3-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclopent Examples of suitable amines include norbornene dicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,4-(2-norbornene)dicarboxylic acid, 5-norbornene-2,3-dicarboxylic acid, bicyclo[2.2.2]octane-1,4-dicarboxylic acid, bicyclo[2.2.2]octane-2,3-dicarboxylic acid, 2,5-dioxo-1,4-bicyclo[2.2.2]octanedicarboxylic acid, 1,3-adamantanedicarboxylic acid, 4,8-dioxo-1,3-adamantanedicarboxylic acid, 2,6-spiro[3.3]heptanedicarboxylic acid, 1,3-adamantanediacetic acid, and camphoric acid.
[0047] Examples of aromatic dicarboxylic acids include o-phthalic acid, isophthalic acid, terephthalic acid, 5-methylisophthalic acid, 5-tert-butylisophthalic acid, 5-aminoisophthalic acid, 5-hydroxyisophthalic acid, 2,5-dimethylterephthalic acid, tetramethylterephthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-anthracenedicarboxylic acid, 1,4-anthraquinonedicarboxylic acid, 2,5-biphenyldicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 1,5-biphenylenedicarboxylic acid, 4,4"-terphenyldicarboxylic acid, 4,4'-diphenylmethanedicarboxylic acid, 4,4'-diphenylethanedicarboxylic acid, 4,4'-diphenylpropanedicarboxylic acid, 4,4'-diphenyl Examples of dicarboxylic acids include hexafluoropropane dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-bibenzyl dicarboxylic acid, 4,4'-stilbene dicarboxylic acid, 4,4'-trans dicarboxylic acid, 4,4'-carbonyl dibenzoic acid, 4,4'-sulfonyl dibenzoic acid, 4,4'-dithio dibenzoic acid, p-phenylene diacetic acid, 3,3'-p-phenylene dipropionic acid, 4-carboxycinnamic acid, p-phenylene diacrylic acid, 3,3'-[4,4'-(methylene di-p-phenylene)] dipropionic acid, 4,4'-[4,4'-(oxydi-p-phenylene)] dipropionic acid, 4,4'-[4,4'-(oxydi-p-phenylene)] dibutyric acid, (isopropylidenedi-p-phenylenedioxy) dibutyric acid, and bis(p-carboxyphenyl) dimethylsilane.
[0048] Examples of dicarboxylic acids containing a heterocycle include 1,5-(9-oxofluorene)dicarboxylic acid, 3,4-furandicarboxylic acid, 4,5-thiazoledicarboxylic acid, 2-phenyl-4,5-thiazoledicarboxylic acid, 1,2,5-thiadiazole-3,4-dicarboxylic acid, 1,2,5-oxadiazole-3,4-dicarboxylic acid, 2,3-pyridinedicarboxylic acid, 2,4-pyridinedicarboxylic acid, 2,5-pyridinedicarboxylic acid, 2,6-pyridinedicarboxylic acid, 3,4-pyridinedicarboxylic acid, and 3,5-pyridinedicarboxylic acid.
[0049] The above-mentioned various dicarboxylic acids may have an acid dihalide or anhydride structure. It is preferable that these dicarboxylic acids are capable of giving a polyamide having a linear structure, in order to maintain the alignment of liquid crystal molecules. Among these, terephthalic acid, isoterephthalic acid, 1,4-cyclohexanedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 4,4'-diphenylmethanedicarboxylic acid, 4,4'-diphenylethanedicarboxylic acid, 4,4'-diphenylpropanedicarboxylic acid, 4,4'-diphenylhexafluoropropanedicarboxylic acid, 2,2-bis(phenyl)propanedicarboxylic acid, 4,4"-terphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,5-pyridinedicarboxylic acid, or acid dihalides thereof are preferably used. Some of these compounds have isomers, and mixtures containing them may be used. Two or more compounds may be used in combination. The dicarboxylic acids used in the present invention are not limited to the above-mentioned exemplary compounds.
[0050] The polyimide having the divalent group represented by formula (1) in the main chain may be a polyimide obtained by ring-closing the above-mentioned polyimide precursor. In this polyimide, the ring-closing rate of the amic acid group (also called the imidization rate) does not necessarily have to be 100% and can be adjusted as desired depending on the application or purpose. Methods for imidizing the polyimide precursor include thermal imidization, in which a solution of the polyimide precursor is heated as is, and catalytic imidization, in which a catalyst is added to a solution of the polyimide precursor.
[0051] A known synthesis method can be used to obtain polyamic acid, polyamic acid ester, polyurea, or polyamide by reacting a diamine (also referred to as a "diamine component") as a raw material with a component selected from a tetracarboxylic dianhydride (also referred to as a "tetracarboxylic dianhydride component"), a tetracarboxylic diester, a diisocyanate, and a dicarboxylic acid as raw materials. Generally, the method involves reacting a diamine component with one or more components selected from a tetracarboxylic dianhydride component, a tetracarboxylic diester, a diisocyanate, and a dicarboxylic acid in an organic solvent.
[0052] The reaction between the diamine component and the tetracarboxylic dianhydride component is advantageous in that it proceeds relatively easily in an organic solvent and does not produce by-products.
[0053] The organic solvent used in the reaction is not particularly limited as long as the polymer produced is soluble in the organic solvent. Furthermore, even if the polymer is not soluble in the organic solvent, it may be mixed with the above-mentioned solvent to the extent that the polymer produced does not precipitate. Note that, since the moisture in the organic solvent inhibits the polymerization reaction and further causes the polymer produced to be hydrolyzed, it is preferable to use the organic solvent that has been dehydrated and dried.
[0054] Examples of the organic solvent include N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N-methylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, 3-methoxy-N,N-dimethylpropanamide, N-methylcaprolactam, dimethylsulfoxide, tetramethylurea, pyridine, dimethylsulfone, hexamethylphosphoric triamide, γ-butyrolactone, isopropyl alcohol, methoxymethylpentanol, diphenylmethane, ethylhexyl ether, butyl ether, isopropyl alcohol ... ethyl amyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isoamyl ketone, methyl isopropyl ketone, methyl cellosolve, ethyl cellosolve, methyl cellosolve acetate, butyl cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethacrylate ethyl ether, propylene glycol monobutyl ether, propylene glycol-tert-butyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, diethylene glycol, diethylene glycol monoacetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methylcyclohexene, propyl ether, dihexyl ether, dioxane, n-hexane, n-pentane, n-octane,Examples of the organic solvent include diethyl ether, cyclohexanone, ethylene carbonate, propylene carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, diglyme, 4-hydroxy-4-methyl-2-pentanone, and 2-ethyl-1-hexanol. These organic solvents may be used alone or in combination.
[0055] When the diamine component and the tetracarboxylic dianhydride component are reacted in an organic solvent, any of the following methods may be used: a solution in which the diamine component is dispersed or dissolved in an organic solvent is stirred, and the tetracarboxylic dianhydride component is added as is or after being dispersed or dissolved in an organic solvent; a method in which the diamine component is added to a solution in which the tetracarboxylic dianhydride component is dispersed or dissolved in an organic solvent; a method in which the tetracarboxylic dianhydride component and the diamine component are added alternately; etc. In addition, when the diamine component or the tetracarboxylic dianhydride component is composed of a plurality of kinds of compounds, they may be reacted in a premixed state, or may be reacted individually in sequence, and low molecular weight compounds that have been reacted individually may be mixed and reacted to form a high molecular weight compound.
[0056] The temperature at which the diamine component and the tetracarboxylic dianhydride component are reacted can be selected arbitrarily, for example, within the range of −20 to 100° C., and preferably −5 to 80° C. The reaction can be carried out at an arbitrary concentration, and for example, the total amount of the diamine component and the tetracarboxylic dianhydride component relative to the reaction liquid is 1 to 50% by mass, and preferably 5 to 30% by mass.
[0057] In the above polymerization reaction, the ratio of the total number of moles of the tetracarboxylic dianhydride components to the total number of moles of the diamine components can be selected at any value depending on the molecular weight of the polyamic acid to be obtained. As in the case of a normal polycondensation reaction, the closer this molar ratio is to 1.0, the larger the molecular weight of the polyamic acid to be produced. The preferred range is 0.8 to 1.2.
[0058] The method for synthesizing the polymer used in the present invention is not limited to the above-mentioned method. When synthesizing a polyamic acid, a tetracarboxylic acid derivative such as a tetracarboxylic acid or a tetracarboxylic acid dihalide having a corresponding structure can be used instead of the above-mentioned tetracarboxylic acid dianhydride in the same manner as in the general polyamic acid synthesis method, and the corresponding polyamic acid can be obtained by reacting them by a known method. In addition, when synthesizing a polyurea, a diamine can be reacted with a diisocyanate. When producing a polyamic acid ester or polyamide, a diamine and a component selected from a tetracarboxylic acid diester and a dicarboxylic acid can be reacted with a diamine in the presence of a known condensing agent or after being derived into an acid halide by a known method.
[0059] The method of imidizing the above-mentioned polyamic acid to obtain a polyimide includes thermal imidization in which a solution of polyamic acid is heated as is, and catalytic imidization in which a catalyst is added to a solution of polyamic acid. The imidization rate from polyamic acid to polyimide is preferably 30% or more, more preferably 30 to 99%, because it can increase the voltage retention rate. On the other hand, from the viewpoint of whitening characteristics, that is, suppressing precipitation of polymers in the varnish, it is preferably 70% or less. Taking both characteristics into consideration, it is more preferably 40 to 80%.
[0060] The temperature when thermally imidizing the polyamic acid in a solution is usually 100 to 400° C., preferably 120 to 250° C., and it is preferable to carry out the imidization while removing water generated by the imidization reaction from the system.
[0061] The catalytic imidization of polyamic acid can be carried out by adding a basic catalyst and an acid anhydride to a solution of polyamic acid and stirring the mixture at -20 to 250°C, preferably 0 to 180°C. The amount of the basic catalyst is usually 0.5 to 30 times by mol, preferably 2 to 20 times by mol, the amount of the acid anhydride is usually 1 to 50 times by mol, preferably 3 to 30 times by mol, the amount of the amic acid group. Examples of the basic catalyst include pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc., among which pyridine is preferred because it has a suitable basicity for promoting the reaction. Examples of the acid anhydride include acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc., among which acetic anhydride is preferred because it facilitates purification after the reaction. The imidization rate by catalytic imidization can be controlled by adjusting the amount of the catalyst, the reaction temperature, the reaction time, etc.
[0062] When recovering the polymer generated from the reaction solution of the polymer, the reaction solution may be poured into a poor solvent to cause precipitation. Examples of poor solvents used for precipitation include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, and water. The polymer precipitated by pouring into the poor solvent can be recovered by filtration, and then dried at room temperature or by heating under normal or reduced pressure. In addition, the polymer precipitated and recovered can be redissolved in an organic solvent and the reprecipitation and recovery operation can be repeated 2 to 10 times to reduce impurities in the polymer. Examples of poor solvents in this case include alcohols, ketones, and hydrocarbons, and it is preferable to use three or more poor solvents selected from these because the efficiency of purification is further improved.
[0063] From the viewpoint of use as a liquid crystal aligning agent, the polymer that is the component (A) of the present invention is more preferably at least one selected from a polyimide precursor containing a structural unit represented by the following formula (6) and a polyimide that is an imidized product thereof. [ka] In the above formula (6), X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y1 is a divalent organic group derived from the diamine of formula (2), and R4 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. R4 is preferably a hydrogen atom, a methyl group, or an ethyl group from the viewpoint of ease of imidization by heating.
[0064] <Tetracarboxylic acid dianhydride> X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and its structure is not particularly limited. X1 in the polyimide precursor is appropriately selected depending on the degree of required properties, such as the solubility of the polymer in a solvent, the applicability of the liquid crystal alignment agent, the alignment of the liquid crystal when made into a liquid crystal alignment film, the voltage holding ratio, the stored charge, etc., and one type of X1 may be present in the same polymer, or two or more types may be present in the same polymer. Specific examples of X1 include structures of formulas (X-1) to (X-46) shown in pages 13 and 14 of WO 2015 / 119168.
[0065] Preferred structures of X1 are shown below, but the present invention is not limited to these. [ka]
[0066] [ka] Of the above structures, (A-1) and (A-2) are particularly preferred from the viewpoint of photoalignment, (A-4) is particularly preferred from the viewpoint of further improving the relaxation speed of the accumulated charge, and (A-15) to (A-17) and the like are particularly preferred from the viewpoint of further improving the liquid crystal alignment and the relaxation speed of the accumulated charge.
[0067] <Polymers (other structural units)> The polyimide precursor containing the structural unit represented by formula (6) may contain at least one selected from the structural unit represented by formula (7) below and polyimide which is an imidized product thereof, within the range not impairing the effects of the present invention. [ka] In formula (7), X2 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y2 is a divalent organic group derived from a diamine not containing the structure of formula (1), R5 is defined as R4 in formula (6) above and represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and R6 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. In addition, it is preferable that at least one of the two R6 is a hydrogen atom.
[0068] Specific examples of X2 include the same structures as those exemplified for X1 in formula (6), including preferred examples. Y2 in the polyimide precursor is a divalent organic group derived from a diamine that does not contain the structure of formula (1), and its structure is not particularly limited. Y2 is appropriately selected depending on the degree of required properties, such as the solubility of the polymer in a solvent, the coatability of the liquid crystal alignment agent, the alignment of the liquid crystal when made into a liquid crystal alignment film, the voltage holding rate, and the stored charge, and may be one type or two or more types mixed in the same polymer.
[0069] Specific examples of Y2 include the structure of formula (2) described in paragraph 4 of WO 2015 / 119168 and the structures of formulae (Y-1) to (Y-97) and (Y-101) to (Y-118) described in paragraphs 8 to 12 of WO 2015 / 119168; a divalent organic group having two amino groups removed from formula (2) described in paragraph 6 of WO 2013 / 008906; a divalent organic group obtained by removing two amino groups from formula (1) described in paragraph 8 of WO 2015 / 060360; a divalent organic group obtained by removing two amino groups from formula (1) described in paragraph 8 of JP 2012-173514; and a divalent organic group obtained by removing two amino groups from formulas (A) to (F) described in paragraph 9 of WO 2010-050523.
[0070] Preferred structures of Y2 are shown below, but the present invention is not limited to these. [ka]
[0071] [ka]
[0072] [ka]
[0073] [ka]
[0074] Of the above structures, (B-28) and (B-29) are particularly preferred from the viewpoint of further improving film hardness, (B-1) to (B-3) are particularly preferred from the viewpoint of further improving liquid crystal alignment, (B-14) to (B-18) and (B-27) are particularly preferred from the viewpoint of further improving the relaxation rate of accumulated charges, and (B-26) is preferred from the viewpoint of further improving the voltage holding ratio.
[0075] When a polyimide precursor containing a structural unit represented by formula (6) also contains a structural unit represented by formula (7), the structural unit represented by formula (6) is preferably 5 mol % to 80 mol %, more preferably 10 mol % to 50 mol %, based on the total of formulas (6) and (7).
[0076] The polyimide having the divalent group represented by formula (1) in the main chain may be a polyimide obtained by ring-closing the above-mentioned polyimide precursor. In this polyimide, the ring-closing rate of the amic acid group (also called the imidization rate) does not necessarily have to be 100% and can be adjusted as desired depending on the application or purpose. Methods for imidizing the polyimide precursor include thermal imidization, in which a solution of the polyimide precursor is heated as is, and catalytic imidization, in which a catalyst is added to a solution of the polyimide precursor.
[0077] <(B) component> The polymer (B) component contained in the radical-generating film-forming composition of the present invention is preferably a polymer obtained by using a diamine.Specific examples include polyamic acid, polyamic acid ester, polyimide, polyurea, polyamide, etc., but from the viewpoint of use as a radical-generating film-forming composition, it is more preferable to use at least one selected from the structural unit represented by the above formula (6) and the structural unit represented by the above formula (7), a polyimide precursor containing only the structural unit represented by the above formula (7), and a polyimide which is an imidized product thereof.Preferred tetracarboxylic dianhydrides and diamines are as exemplified in the above formula (7).
[0078] In addition, in the radical-generating film-forming composition as a liquid crystal aligning agent of the present invention, it is preferable that neither the polymer of component (A) nor the polymer of component (B) contains a vertical alignment group for vertically aligning the liquid crystal.
[0079] In addition, when the radical-generating film is made of a polymer containing an organic group that induces radical polymerization, the radical-generating film-forming composition used in the present invention may contain a polymer other than the polymer containing an organic group that induces radical polymerization. In this case, the content of the other polymer in the total polymer components is preferably 5 to 95 mass %, more preferably 30 to 70 mass %.
[0080] The molecular weight of the polymer having the radical-generating film-forming composition is preferably 5,000 to 1,000,000, and more preferably 10,000 to 150,000, in terms of weight-average molecular weight measured by GPC (Gel Permeation Chromatography), taking into consideration the strength of the radical-generating film obtained by applying the radical-generating film-forming composition, the workability during film formation, the uniformity of the film, and the like.
[0081] The radical-generating film-forming composition may contain an organic solvent that dissolves or disperses the polymer component and, if necessary, other components. Such organic solvents are not particularly limited, and examples thereof include the organic solvents exemplified in the synthesis of the polyamic acid described above. Among them, N-methyl-2-pyrrolidone, γ-butyrolactone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, 3-methoxy-N,N-dimethylpropanamide, etc. are preferred from the viewpoint of solubility. In particular, N-methyl-2-pyrrolidone or N-ethyl-2-pyrrolidone is preferred, but a mixed solvent of two or more kinds may be used.
[0082] In addition, it is preferable to use a solvent that improves the uniformity and smoothness of the coating film by mixing it with an organic solvent in which the components contained in the radical-generating film-forming composition are highly soluble.
[0083] Examples of solvents that improve the uniformity and smoothness of the coating film include isopropyl alcohol, methoxymethyl pentanol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl cellosolve acetate, butyl cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethyl carbitol acetate, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol monobutyl ether, propylene glycol-tert-butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene glycol monoacetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methylcyclohexene, propyl ether, dihexyl ether, n-hexa , n-pentane, n-octane, diethyl ether, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, 1-methoxy-2-propanol,Examples of the solvent include 1-ethoxy-2-propanol, 1-butoxy-2-propanol, 1-phenoxy-2-propanol, propylene glycol monoacetate, propylene glycol diacetate, propylene glycol-1-monomethyl ether-2-acetate, propylene glycol-1-monoethyl ether-2-acetate, dipropylene glycol, 2-(2-ethoxypropoxy)propanol, and 2-ethyl-1-hexanol. A plurality of these solvents may be mixed. When using these solvents, the amount is preferably 5 to 80% by mass, more preferably 20 to 60% by mass, of the total solvent contained in the liquid crystal alignment agent.
[0084] The radical-generating film-forming composition of the present invention may additionally contain components other than the polymer component and the organic solvent. Such additional components include an adhesion assistant for improving the adhesion between the radical-generating film and a substrate or between the radical-generating film and a sealant, a compound for increasing the strength of the radical-generating film (hereinafter also referred to as a crosslinking compound), a dielectric or conductive material for adjusting the dielectric constant or electrical resistance of the radical-generating film, etc.
[0085] As the crosslinkable compound, from the viewpoints of generating less AC afterimages and having a high effect of improving film strength, a compound having two or more types of at least one group selected from the group consisting of an oxiranyl group, an oxetanyl group, a protected isocyanate group, a protected isothiocyanate group, a group containing an oxazoline ring structure, a group containing a Meldrum's acid structure, a cyclocarbonate group, and a group represented by the following formula (d), or a compound selected from compounds represented by the following formula (e) (hereinafter these are collectively referred to as compound (C)). [ka] (In the formula, R 71 and R 72 each independently represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or the group "*-CH2-OH". * represents a bond. A represents an organic group having a valence of (m+n) and an aromatic ring. m represents an integer of 1 to 6, and n represents an integer of 0 to 4. R 73represents an alkyl group having 1 to 5 carbon atoms.
[0086] Specific examples of compounds having an oxiranyl group include compounds having two or more oxiranyl groups, such as the compounds described in paragraph
[0037] of JP-A-10-338880 and compounds having a triazine ring skeleton described in International Publication WO2017 / 170483. Among these, compounds containing nitrogen atoms, such as N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N,N',N'-tetraglycidyl-p-phenylenediamine, and compounds represented by the following formulas (r-1) to (r-3), are particularly preferred. [ka]
[0087] Specific examples of the compound having an oxetanyl group include compounds having two or more oxetanyl groups described in paragraphs
[0170] to
[0175] of WO 2011 / 132751.
[0088] Specific examples of the compound having a protected isocyanate group include the compounds having two or more protected isocyanate groups described in paragraphs
[0046] to
[0047] of JP 2014-224978 A, and the compounds having three or more protected isocyanate groups described in paragraphs
[0119] to
[0120] of WO 2015 / 141598 A. Among these, the compounds represented by the following formulae (bi-1) to (bi-3) are preferred. [ka]
[0089] Specific examples of compounds having a protected isothiocyanate group include compounds having two or more protected isothiocyanate groups, as described in JP-A-2016-200798.
[0090] Specific examples of the compound having a group containing an oxazoline ring structure include compounds containing two or more oxazoline structures, as described in paragraph
[0115] of JP-A-2007-286597.
[0091] Specific examples of the compound having a group containing a Meldrum's acid structure include compounds having two or more Meldrum's acid structures, as described in International Publication WO2012 / 091088.
[0092] Specific examples of the compound having a cyclocarbonate group include compounds described in International Publication WO2011 / 155577.
[0093] R of the group represented by the above formula (d) 71 , R 72 Examples of the alkyl group having 1 to 3 carbon atoms include a methyl group, an ethyl group, and a propyl group.
[0094] Specific examples of the compound having a group represented by the above formula (d) include compounds having two or more groups represented by the above formula (d) described in International Publication WO2015 / 072554 and paragraph
[0058] of JP2016-118753A, compounds described in JP2016-200798A, etc. Among these, the compounds represented by the following formulae (hd-1) to (hd-8) are preferred. [ka]
[0095] Examples of the (m+n)-valent organic group having an aromatic ring in A of the above formula (e) include an (m+n)-valent aromatic hydrocarbon group having 5 to 30 carbon atoms, an (m+n)-valent organic group to which an aromatic hydrocarbon group having 5 to 30 carbon atoms is bonded directly or via a linking group, and an (m+n)-valent group having an aromatic heterocycle. Examples of the aromatic hydrocarbon include benzene and naphthalene. Examples of the aromatic heterocycle include a pyrrole ring, an imidazole ring, a pyrazole ring, a pyridine ring, a pyrimidine ring, a quinoline ring, an isoquinoline ring, a carbazole ring, a pyridazine ring, a pyrazine ring, a benzimidazole ring, a benzimidazole ring, an indole ring, a quinoxaline ring, and an acridine ring. Examples of the linking group include an alkylene group having 1 to 10 carbon atoms, a group obtained by removing one hydrogen atom from the above alkylene group, and a divalent or trivalent cyclohexane ring. Any hydrogen atom in the alkylene group may be substituted with an organic group such as an alkyl group having 1 to 6 carbon atoms, a fluorine atom, or a trifluoromethyl group. 73 Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, etc. Specific examples include the compounds described in International Publication WO2010 / 074269.
[0096] Preferred specific examples include the following formulae (e-1) to (e-9). [ka]
[0097] The above compounds are examples of crosslinkable compounds, and are not limited thereto. For example, components other than those described above disclosed on pages 53
[0105] to 55
[0116] of International Publication No. 2015 / 060357 can be mentioned. The crosslinkable compound contained in the radical-generating film-forming composition of the present invention may be one type, or two or more types may be combined. The content of the crosslinkable compound in the radical-generating film-forming composition of the present invention is preferably 0.5 to 20 parts by mass relative to 100 parts by mass of the polymer component contained in the radical-generating film-forming composition, and from the viewpoints of proceeding with the crosslinking reaction to exhibit the intended effect and minimizing the occurrence of AC afterimages, the content is more preferably 1 to 15 parts by mass.
[0098] Examples of the adhesion aid include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldiethoxymethylsilane, 2-aminopropyltrimethoxysilane, 2-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltriethoxysilane, N-triethoxysilylpropyltriethylenetriamine, N-trimethoxy ... triethylenetriamine, 10-trimethoxysilyl-1,4,7-triazadecane, 10-triethoxysilyl-1,4,7-triazadecane, 9-trimethoxysilyl-3,6-diazanonyl acetate, 9-triethoxysilyl-3,6-diazanonyl acetate, N-benzyl-3-aminopropyltrimethoxysilane, N-benzyl-3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, N-bis(oxyethylene)-3-aminopropyltrimethoxysilane, N-bis(oxyethylene)-3-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,Examples of silane coupling agents include 4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane. When using these silane coupling agents, the amount is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, per 100 parts by mass of the polymer component contained in the liquid crystal alignment agent, from the viewpoint of reducing the occurrence of AC afterimages.
[0099] Furthermore, in addition to the above, the radical-generating film-forming composition may contain a dielectric or conductive substance for the purpose of changing the electrical properties, such as the dielectric constant and conductivity, of the radical-generating film, as long as the effects of the present invention are not impaired.
[0100] The radical-generating film-forming composition of the present invention is a liquid crystal aligning agent having radical generating ability, and the liquid crystal alignment film obtained from the radical-generating film-forming composition is particularly referred to as a radical-generating film in this specification.
[0101] (Radical generating film and liquid crystal alignment film) The radical-generating film of this embodiment is obtained by using the radical-generating film-forming composition. For example, the radical-generating film-forming composition used in the present invention is applied to a substrate, and then dried and baked to obtain a cured film, which can be used as it is as a radical-generating film. In addition, this cured film can be rubbed, irradiated with polarized light or light of a specific wavelength, or treated with an ion beam, or irradiated with UV light on a liquid crystal display element filled with liquid crystal as an alignment film for PSA.
[0102] Examples of methods for applying the radical-generating film-forming composition include spin coating, printing, inkjet, spraying, and roll coating. From the viewpoint of productivity, the transfer printing method is widely used industrially and is also preferably used in the present invention.
[0103] The substrate to which the radical-generating film-forming composition is applied is not particularly limited as long as it is a highly transparent substrate. Specific examples include glass plates, plastic plates such as polycarbonate, poly(meth)acrylate, polyethersulfone, polyarylate, polyurethane, polysulfone, polyether, polyetherketone, trimethylpentene, polyolefin, polyethylene terephthalate, (meth)acrylonitrile, triacetyl cellulose, diacetyl cellulose, and acetate butyrate cellulose.
[0104] The drying step after coating the radical-generating film-forming composition is not necessarily required, but when the time from coating to baking is not constant for each substrate, or baking is not performed immediately after coating, it is preferable to include a drying step. This drying is sufficient as long as the solvent is removed to an extent that the coating film shape is not deformed by transportation of the substrate, and the drying method is not particularly limited. For example, a method of drying on a hot plate at a temperature of 40 to 150°C, preferably 60 to 100°C, for 0.5 to 30 minutes, preferably 1 to 5 minutes, can be mentioned.
[0105] The coating film formed by applying the radical-generating film-forming composition by the above method can be baked to form a cured film. The baking temperature can be any temperature between 100 and 350°C, preferably between 140 and 300°C, more preferably between 150 and 230°C, and even more preferably between 160 and 220°C. The baking time can be any time between 5 and 240 minutes, preferably between 10 and 90 minutes, and more preferably between 20 and 90 minutes. Heating can be performed by a commonly known method, such as a hot plate, a hot air circulation oven, an IR (infrared) oven, or a belt furnace.
[0106] The thickness of the cured film can be selected as necessary, but is preferably 5 nm or more, more preferably 10 nm or more, since the reliability of the liquid crystal display element is easily obtained. Also, the thickness of the cured film is preferably 300 nm or less, more preferably 150 nm or less, since the power consumption of the liquid crystal display element is not extremely large.
[0107] A substrate having a radical generating film can be obtained in the manner described above, and the radical generating film can be subjected to a uniaxial alignment treatment. Methods for carrying out the uniaxial alignment treatment include photoalignment, oblique deposition, rubbing, and uniaxial alignment treatment using a magnetic field.
[0108] When performing alignment treatment by unidirectional rubbing, for example, a rubbing roller wrapped with a rubbing cloth is rotated while the substrate is moved so that the rubbing cloth comes into contact with the film.
[0109] When the coating film is given liquid crystal alignment ability by photo-alignment treatment, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm can be used as radiation to be irradiated to the coating film. When the radiation is polarized, it may be linearly polarized or partially polarized. When the radiation used is linearly polarized or partially polarized, the radiation may be applied from a direction perpendicular to the substrate surface, from an oblique direction, or a combination of these. When applying non-polarized radiation, the radiation is applied in an oblique direction.
[0110] Examples of light sources that can be used include low-pressure mercury lamps, high-pressure mercury lamps, deuterium lamps, metal halide lamps, argon resonance lamps, xenon lamps, and excimer lasers. Ultraviolet rays in a preferred wavelength range can be obtained by using a light source in combination with, for example, a filter, a diffraction grating, and the like. The radiation dose is preferably 10 to 2,000 mJ / cm. 2 and more preferably 30 to 1,000 mJ / cm 2 It is.
[0111] The coating film may be irradiated with light while being heated in order to enhance reactivity. The temperature during heating is usually 30 to 250°C, preferably 40 to 200°C, and more preferably 50 to 150°C.
[0112] When ultraviolet light containing light having a wavelength of 150 to 800 nm is used, the light-irradiated film obtained in the above process can be used as a liquid crystal alignment film as it is, but the light-irradiated film may be baked, washed with water or an organic solvent, or a combination of these. The baking temperature is preferably 80 to 300°C, more preferably 80 to 250°C. The baking time is preferably 5 to 200 minutes, more preferably 10 to 100 minutes. The baking may be performed once or twice or more. The photo-alignment treatment here corresponds to a treatment of light irradiation in a state where the film is not in contact with the liquid crystal layer.
[0113] The organic solvent used for the washing is not particularly limited, but specific examples include methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propyl acetate, butyl acetate, and cyclohexyl acetate.
[0114] The liquid crystal cell of the present invention can use the above-mentioned radical generating film of the present invention as the liquid crystal alignment film arranged on one substrate side, and can use a liquid crystal alignment film that is commonly used as a liquid crystal alignment film as the liquid crystal alignment film arranged on the other substrate side. The liquid crystal alignment film of this embodiment to be disposed on the other substrate side is obtained by the same method as for the radical generating film, except that a commonly used liquid crystal alignment agent is used instead of the radical generating film forming composition.
[0115] As the substrate to which the radical-generating film-forming composition is applied and the substrate to which the liquid crystal alignment agent is applied, a substrate having a transparent electrode for driving the liquid crystal formed on one of the substrates listed above is preferred. Substrates that can be used in IPS liquid crystal display elements can also have electrode patterns such as standard IPS comb electrodes and PSA fishbone electrodes, or protrusion patterns such as MVA. Moreover, in highly functional elements such as TFT type elements, elements such as transistors are formed between electrodes for driving liquid crystal and a substrate.
[0116] When a transmissive liquid crystal display element is intended, the above-mentioned substrates are generally used, but when a reflective liquid crystal display element is intended, an opaque substrate such as a silicon wafer can be used for only one of the substrates. In that case, a material such as aluminum that reflects light can be used for the electrodes formed on the substrate.
[0117] When rubbing a liquid crystal alignment film on a substrate on which comb-tooth electrodes are formed, the rubbing direction is selected depending on the electrical properties of the liquid crystal. When using a liquid crystal having positive dielectric anisotropy, it is preferable that the rubbing direction be approximately the same as the direction in which the comb-tooth electrodes extend.
[0118] (Liquid crystal cell) The liquid crystal cell of the present invention is obtained by arranging a substrate (first substrate) having a liquid crystal alignment film and a substrate (second substrate) having a radical generating film formed thereon by the above-mentioned method so that the radical generating film and the liquid crystal alignment film face each other, sandwiching a spacer between them, fixing them with a sealant, injecting a liquid crystal composition containing liquid crystal and a radical polymerizable compound, and sealing it. In this case, the size of the spacer used is usually 1 to 30 μm, but preferably 2 to 10 μm. In addition, by arranging the alignment direction of the first substrate and the alignment direction of the second substrate parallel to each other, it can be used in IPS mode or FFS mode, and by arranging them so that the rubbing directions are perpendicular to each other, it can be used in twisted nematic mode. It is preferable that either the first substrate or the second substrate is a comb-tooth electrode substrate. The alignment film formed on the first substrate may be either a known liquid crystal alignment film or a radical-generating film according to the present invention, and can be appropriately selected depending on the purpose. The alignment film formed on the first substrate may be subjected to a uniaxial alignment treatment. It is also preferable to form a liquid crystal alignment film for horizontal alignment, which has been subjected to uniaxial alignment treatment, on the first substrate.
[0119] The method for injecting the liquid crystal composition containing the liquid crystal and the radical polymerizable compound is not particularly limited, and examples thereof include a vacuum method in which the pressure inside the prepared liquid crystal cell is reduced and then a mixture containing the liquid crystal and the polymerizable compound is injected, and a dropping method in which a mixture containing the liquid crystal and the polymerizable compound is dropped and then sealed.
[0120] <Liquid crystal composition containing liquid crystal and radically polymerizable compound> In the preparation of the liquid crystal display element of the present invention, the polymerizable compound used together with the liquid crystal is not particularly limited as long as it is a radically polymerizable compound, and is, for example, a compound having one or more polymerizable reactive groups in one molecule. A compound having one polymerizable reactive group in one molecule is preferable (hereinafter, sometimes referred to as a "compound having a monofunctional polymerizable group" or a "compound having a monofunctional polymerizable group"). The polymerizable reactive group is preferably a radically polymerizable reactive group, for example, a vinyl bond.
[0121] At least one of the radically polymerizable compounds is preferably a compound having compatibility with liquid crystal and one polymerizable reactive group in one molecule, that is, a compound having a monofunctional radically polymerizable group.
[0122] The polymerizable group of the radically polymerizable compound is preferably a polymerizable group selected from the following structures. [ka] (In the formula, * indicates the bonding site with the part of the compound molecule other than the polymerizable reactive group. b represents a linear alkyl group having 2 to 8 carbon atoms, and E represents a single bond, -O-, or -NR c R represents a linking group selected from -, -S-, an ester bond, and an amide bond. c represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0123] In addition, in the liquid crystal composition containing the above liquid crystal and a radical polymerizable compound, it is preferable to contain a radical polymerizable compound that will give a polymer having a Tg of 100° C. or less when the radical polymerizable compound is polymerized.
[0124] The compound having a monofunctional radically polymerizable group has a reactive group capable of undergoing radical polymerization in the presence of an organic radical, and examples of the compound include methacrylate monomers such as tert-butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, lauryl methacrylate, and n-octyl methacrylate; acrylate monomers such as tert-butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, benzyl acrylate, lauryl acrylate, and n-octyl acrylate; styrene and styrene derivatives (e.g., o-, m-, and p-methoxystyrene, o-, m-, and p-tert-butoxy ... Examples of the vinyl monomer include vinyl monomers such as vinyl esters (e.g., vinyl acetate, vinyl propionate, vinyl benzoate, vinyl acetate, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl hexyl ketone, methyl isopropenyl ketone, etc.), N-vinyl compounds (e.g., N-vinyl pyrrolidone, N-vinyl pyrrole, N-vinyl carbazole, N-vinyl indole, etc.), (meth)acrylic acid derivatives (e.g., acrylonitrile, methacrylonitrile, acrylamide, isopropyl acrylamide, methacrylamide, etc.), and vinyl halides (e.g., vinyl chloride, vinylidene chloride, tetrachloroethylene, hexachloropropene, vinyl fluoride, etc.), but are not limited thereto. These various radical polymerizable monomers may be used alone or in combination of two or more. In addition, it is preferable that these have compatibility with the liquid crystal.
[0125] Furthermore, as the radically polymerizable compound, a compound represented by the following formula (A) is also preferred. [ka] (In formula (A), R a and R b each independently represents a linear alkyl group having 2 to 8 carbon atoms, and E represents a single bond, -O-, or -NR c Represents a bond selected from -, -S-, an ester bond, and an amide bond.c represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0126] At least one of the radically polymerizable compounds is preferably a compound having compatibility with liquid crystal and one polymerizable reactive group in one molecule, that is, a compound having a monofunctional radically polymerizable group.
[0127] As the radical polymerizable compound represented by the above formula (A), one in which E is an ester bond (a bond represented by -C(=O)-O- or -OC(=O)-) is preferred from the viewpoints of ease of synthesis, compatibility with liquid crystal, and polymerization reactivity. Specifically, a compound having the following structure is preferred, but there is no particular limitation thereon. [ka] (In formulas (A-1) and (A-2), R a and R b each independently represents a linear alkyl group having 2 to 8 carbon atoms.
[0128] The content of the radically polymerizable compound in the liquid crystal composition is preferably 3 mass % or more, more preferably 5 mass % or more, and preferably 50 mass % or less, more preferably 20 mass % or less, relative to the total mass of the liquid crystal and the radically polymerizable compound.
[0129] The polymer obtained by polymerizing the radically polymerizable compound preferably has a Tg of 100° C. or lower.
[0130] Liquid crystal generally refers to a substance that exhibits both solid and liquid properties, and representative liquid crystal phases include nematic liquid crystal and smectic liquid crystal, but the liquid crystal that can be used in the present invention is not particularly limited. One example is 4-pentyl-4'-cyanobiphenyl.
[0131] Next, a liquid crystal cell containing the mixture (liquid crystal composition) containing the liquid crystal and the radical polymerizable compound is given sufficient energy to polymerize the radical polymerizable compound. This can be done, for example, by applying heat or irradiating with UV light, and the radical polymerizable compound is polymerized in situ to develop the desired characteristics. Among these, UV irradiation is preferred because it allows patterning of the alignment and also allows the polymerization reaction to occur in a short time. When using the liquid crystal composition in a twisted nematic mode, a chiral dopant may be introduced into the liquid crystal cell as necessary in addition to the liquid crystal composition.
[0132] The heating temperature during UV irradiation is preferably within a temperature range in which the introduced liquid crystal exhibits liquid crystallinity, and is usually 40° C. or higher, and is preferably below the temperature at which the liquid crystal changes to an isotropic phase.
[0133] In this case, the wavelength of UV irradiation in the case of UV irradiation is preferably selected so as to provide the best reaction quantum yield of the polymerizable compound, and the UV irradiation dose is usually 0.5 to 30 J / cm. 2 However, preferably, it is 1 to 10 J / cm 2 A lower amount of UV irradiation is preferable because it can prevent deterioration in reliability due to damage to the components that make up the liquid crystal display, and also because it can reduce the UV irradiation time, thereby improving the manufacturing takt time.
[0134] When polymerization is performed only by heating, not by UV irradiation, the heating is preferably performed at a temperature range at which the polymerizable compound reacts and which is lower than the decomposition temperature of the liquid crystal, specifically, 100° C. or higher and 150° C. or lower.
[0135] When applying sufficient energy to cause a polymerization reaction of the radical polymerizable compound, it is preferable that no voltage is applied and that the device is in an electric field-free state.
[0136] (Liquid crystal display element) A liquid crystal display device can be produced using the liquid crystal cell thus obtained. For example, this liquid crystal cell can be made into a reflective liquid crystal display element by providing a reflective electrode, a transparent electrode, a λ / 4 plate, a polarizing film, a color filter layer, etc., in accordance with a conventional method, as necessary. Furthermore, if necessary, a backlight, a polarizing plate, a λ / 4 plate, a transparent electrode, a polarizing film, a color filter layer, etc. may be provided in the liquid crystal cell in a conventional manner to form a transmission type liquid crystal display element. FIG. 1 is a schematic cross-sectional view showing an example of a liquid crystal display element according to the present invention, which is an example of an IPS mode liquid crystal display element. In the liquid crystal display element 1 illustrated in Fig. 1, a liquid crystal composition 3 is sandwiched between a comb-tooth electrode substrate 2 having a radical-generating film 2c and a counter substrate 4 having a liquid crystal alignment film 4a. The comb-tooth electrode substrate 2 has a base material 2a, a plurality of linear electrodes 2b formed on the base material 2a and arranged in a comb-tooth shape, and a radical-generating film 2c formed on the base material 2a so as to cover the linear electrodes 2b. The counter substrate 4 has a base material 4b and a liquid crystal alignment film 4a formed on the base material 4b. In this liquid crystal display element 1, when a voltage is applied to the linear electrodes 2b, an electric field is generated between the linear electrodes 2b as indicated by electric force lines L. FIG. 2 is a schematic cross-sectional view showing another example of the liquid crystal display element according to the present invention, which is an example of an FFS mode liquid crystal display element. In the liquid crystal display element 1 illustrated in Fig. 2, a liquid crystal composition 3 is sandwiched between a comb-tooth electrode substrate 2 having a radical-generating film 2h and a counter substrate 4 having a liquid crystal alignment film 4a. The comb-tooth electrode substrate 2 has a base material 2d, a plane electrode 2e formed on the base material 2d, an insulating film 2f formed on the plane electrode 2e, a plurality of linear electrodes 2g formed on the insulating film 2f and arranged in a comb-tooth shape, and a radical-generating film 2h formed on the insulating film 2f so as to cover the linear electrodes 2g. The counter substrate 4 has a base material 4b and a liquid crystal alignment film 4a formed on the base material 4b. In this liquid crystal display element 1, when a voltage is applied to the surface electrodes 2e and the linear electrodes 2g, an electric field is generated between the surface electrodes 2e and the linear electrodes 2g, as indicated by electric force lines L. EXAMPLES
[0137] The present invention will be described in detail with reference to examples, but the present invention is not limited to these examples. The abbreviations of the compounds used in the polymerization of the polymer and the preparation of the film-forming composition, and the methods of evaluating the properties are as follows. [ka]
[0138] [ka] NMP: N-methyl-2-pyrrolidone, BCS: Butyl cellosolve
[0139] <Viscosity measurement> The viscosity of the polyamic acid solution at 25° C. was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample amount of 1.1 mL and a cone rotor TE-1 (1°34′, R24).
[0140] <Molecular weight measurement> The molecular weight was measured by a room temperature GPC (gel permeation chromatography) device, and the number average molecular weight (Mn) and weight average molecular weight (Mw) were calculated as polyethylene glycol and polyethylene oxide equivalent values. GPC apparatus: GPC-101 (Showa Denko K.K.), column: GPC KD-803, GPC KD-805 (Showa Denko K.K.) in series, column temperature: 50℃, eluent: N,N-dimethylformamide (additives: lithium bromide monohydrate (LiBr·H2O) 30mmol / L, phosphoric acid·anhydrous crystal (o-phosphoric acid) 30mmol / L, tetrahydrofuran (THF) 10mL / L), flow rate: 1.0mL / min. Standard samples for preparing a calibration curve: TSK standard polyethylene oxide (molecular weight: approximately 900,000, 150,000, 100,000, and 30,000) (manufactured by Tosoh Corporation) and polyethylene glycol (molecular weight: approximately 12,000, 4,000, and 1,000) (manufactured by Polymer Laboratory Co., Ltd.).
[0141] <Measurement of imidization rate> 20 mg of polyimide powder was placed in an NMR sample tube (Kusano Scientific NMR Sampling Tube Standard φ5), 0.53 mL of deuterated dimethyl sulfoxide (DMSO-d6, 0.05 mass% TMS (tetramethylsilane) mixture) was added, and the mixture was sonicated to completely dissolve. The 500 MHz proton NMR of this solution was measured using a measuring device (JNW-ECA500, manufactured by JEOL Datum Co., Ltd.). The imidization rate was determined by determining a proton derived from a structure that does not change before and after imidization as a reference proton, and using the peak integrated value of this proton and the peak integrated value of a proton derived from the NH of an amide group appearing in the vicinity of 9.5 to 10.0 ppm, according to the following formula. Imidization rate (%) = (1-α·x / y) × 100 In the formula, x is the integrated value of the proton peak derived from the NH of the amide group, y is the integrated value of the peak of the reference proton, and α is the ratio of the number of reference protons to one NH proton of the amide group in the case of polyamic acid (imidization rate 0%).
[0142] <Synthesis of compound DA-5> [ka]
[0143] (1st step) 4,4'-dinitro-[1,1'-biphenyl]-2,2'-dicarboxylic acid (20.0g, 60.2mmol) was charged with tetrahydrofuran (120g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (28.4g, 126mmol), 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (28.0g, 181mmol), and N,N-dimethylaminopyridine (0.735g, 6.02mmol), and stirred at room temperature overnight. After the reaction was completed, the mixture was extracted twice with water / chloroform, and the obtained organic phase was concentrated to obtain a syrup-like brown oil. This was purified by column chromatography using a mixed solvent of ethyl acetate / hexane = 3 / 1 (volume ratio). When the obtained fraction was concentrated, it became a yellow transparent oil, and when it was left to stand, white crystals precipitated from the oil. The precipitated crystals were washed with a slurry of a mixed solvent of ethyl acetate / hexane=3 / 1 (volume ratio), filtered, and dried to obtain compound [1] (yield: 29.8 g, 40.0 mmol, 67% yield). 1 H-NMR(500MHz) in DMSO-d6:8.57(d,J=2.5Hz,2H),8.37(dd,J=8.5Hz,2.5Hz,2H),8.18(d,J=9.0Hz,4H),7.55(d,J=8.5Hz,2H), 6.85(d,J=9.0Hz,4H),5.631(s,2H),4.39-4.35(m,4H),4.02-3.99(m,2H),3.96-3.94(m,2H),1.40(s,12H).
[0144] (2nd process) To the compound [1] (29.8g, 40.0mmol) obtained in the first step, tetrahydrofuran (240g) was added, and the mixture was replaced with nitrogen. Then, 3% platinum carbon (wet product) (2.38g) was added, and the mixture was further replaced with nitrogen. A hydrogen Tedlar bag was attached and the mixture was stirred at room temperature for about 17 hours. After the reaction was completed, the mixture was passed through a membrane filter to remove the platinum carbon, and then concentrated and dried to obtain DA-5 (yield: 27.4g, 40.0mmol, quant). 1H-NMR(500MHz) in DMSO-d6:8.20(dd,J=7.1Hz,1.9Hz,4H),6.99(d,J=2.5Hz,2H),6.92(dd,J=7.3Hz,1.9Hz,4H),6.80(d,J=8.2Hz, 2H),6.67(dd,J=8.2Hz,2.5Hz,2H),5.64(s,2H),5.24(s,4H),4.22(t,J=4.5Hz,4H),4.00(br,4H),1.39(s,12H).
[0145] <Synthesis of polyamic acid and polyimide> <Synthesis Example 1> TC-1 / DA-1, DA-2(50) Polymerization of polyamic acid (PAA-1) DA-1 (1.62g: 15.0mmol), DA-2 (3.66g: 15.0mmol) and NMP (55.4g) were weighed out into a 100mL four-neck flask equipped with a mechanical stirrer and nitrogen inlet tube, and after stirring for a while to dissolve, TC-1 (6.25g: 27.9mmol) and NMP (10.0g) were added and reacted at 40℃ for 6 hours under a nitrogen atmosphere to obtain a polyamic acid solution (PAA-1) with a solid content of 15% by mass. The viscosity was 390mPa·s and the weight-average molecular weight was approximately 32,100.
[0146] <Synthesis Example 2> Polymerization of TC-3 / DA-3(100) polyamic acid (PAA-2) DA-3 (5.73g: 20.0mmol) and NMP (61.8g) were weighed out into a 100mL four-neck flask equipped with a mechanical stirrer and nitrogen inlet tube, and after stirring for a while to dissolve, TC-3 (4.06g: 18.6mmol) and NMP (10.0g) were added and reacted for 6 hours at 23℃ under a nitrogen atmosphere to obtain a polyamic acid solution (PAA-2) with a solid concentration of 12% by mass. The viscosity was 240mPa·s and the weight-average molecular weight was approximately 25,900.
[0147] <Synthesis Example 3> Polymerization of TC-2, TC-4(50) / DA-1, DA-4(50) polyamic acid (PAA-3) DA-1 (1.08g:10.0mmol), DA-4 (3.30g:10.0mmol) and NMP (32.9g) were weighed out into a 50mL 4-neck flask equipped with a mechanical stirrer and a nitrogen inlet tube, and after stirring and dissolving for a while under a nitrogen atmosphere, TC-4 (2.50g:10.0mmol) was added and reacted for 6 hours at 40℃ under a nitrogen atmosphere, TC-2 (1.88g:9.6mmol) and NMP (2.1g) were added and reacted for 12 hours at 40℃ under a nitrogen atmosphere to obtain a polyamic acid solution (PAA-3) with a solid content of 20% by mass. The viscosity was 980mPa·s and the weight average molecular weight was about 35,900.
[0148] <Synthesis Example 4> Synthesis of TC-2, TC-4(50) / DA-1, DA-4(50) Soluble polyimide (SPI-1) The polyamic acid solution (PAA-3) (30.0 g) obtained in the above Synthesis Example 3 was weighed out into a 100 mL eggplant flask equipped with a nitrogen inlet tube, an air-cooling tube, and a stirrer, and NMP (70.0 g), acetic anhydride (3.14 g: 30.9 mmol), and pyridine (1.62 g: 20.6 mmol) were added. The mixture was stirred at room temperature for 30 minutes under a nitrogen atmosphere, and then stirred at 50 ° C for 3 hours. After the reaction was completed, the reaction solution was returned to room temperature, and slowly poured into methanol (300 mL) cooled to 10 ° C to precipitate a solid, and stirred for 10 minutes. The obtained solid was collected by filtration, and the obtained solid was further washed with methanol (100 mL) for 10 minutes by stirring twice, and then dried in a vacuum drying oven at 80 ° C for 6 hours to obtain the target polyimide powder (SPI-1). The imidization rate was 62%.
[0149] <Synthesis Example 5> Polymerization of TC-2, TC-4(50) / DA-4(100) polyamic acid (PAA-4) DA-4 (6.61g: 20.0mmol) and NMP (34.1g) were weighed out into a 50mL 4-neck flask equipped with a mechanical stirrer and a nitrogen inlet tube, and after stirring and dissolving for a while under a nitrogen atmosphere, TC-4 (2.50g: 10.0mmol) was added and reacted for 6 hours at 40℃ under a nitrogen atmosphere, TC-2 (1.92g: 9.8mmol) and NMP (10.0g) were added and reacted for 12 hours at 40℃ under a nitrogen atmosphere to obtain a polyamic acid solution (PAA-4) with a solid content of 20% by mass. The viscosity was 1,120mPa·s and the weight-average molecular weight was approximately 38,400.
[0150] <Synthesis Example 6> Synthesis of TC-2, TC-4(50) / DA-4(100) soluble polyimide (SPI-2) The polyamic acid solution (PAA-4) (30.0 g) obtained in the above Synthesis Example 5 was weighed out into a 100 mL eggplant flask equipped with a nitrogen inlet tube, an air-cooling tube, and a stirrer, and NMP (70.0 g), acetic anhydride (3.33 g: 32.7 mmol), and pyridine (1.72 g: 21.8 mmol) were added. The mixture was stirred at room temperature for 30 minutes under a nitrogen atmosphere, and then stirred at 50 ° C for 3 hours. After the reaction was completed, the reaction solution was returned to room temperature, and slowly poured into methanol (300 mL) cooled to 10 ° C to precipitate a solid, and stirred for 10 minutes. The obtained solid was collected by filtration, and the obtained solid was further washed with methanol (100 mL) for 10 minutes by stirring twice, and then dried in a vacuum drying oven at 80 ° C for 6 hours to obtain the target polyimide powder (SPI-2). The imidization rate was 59%.
[0151] <Synthesis Example 7> TC-1 / DA-2, DA-4(50) Polymerization of polyamic acid (PAA-5) DA-2 (1.57g: 7.00mmol), DA-4 (4.79g: 7.00mmol) and NMP (42.60g) were weighed into a 50mL 4-neck flask equipped with a mechanical stirrer and nitrogen inlet tube, and after stirring for a while to dissolve, TC-1 (2.92g: 13.02mmol) and NMP (10.0g) were added and reacted at 40℃ for 6 hours under a nitrogen atmosphere to obtain a polyamic acid solution (PAA-5). The viscosity was 440mPa·s and the weight average molecular weight was approximately 32,600.
[0152] <Synthesis Example 8> Synthesis of TC-1 / DA-2, DA-4(50) Soluble polyimide (SPI-3) The polyamic acid solution (PAA-5) (30.0 g) obtained in the above Synthesis Example 7 was weighed out into a 100 mL eggplant flask equipped with a nitrogen inlet tube, an air-cooled tube, and a stirrer, and NMP (45.0 g), acetic anhydride (1.85 g: 18.0 mmol), and pyridine (0.95 g: 12.0 mmol) were added. The mixture was stirred at room temperature for 30 minutes under a nitrogen atmosphere, and then stirred at 50°C for 3 hours. After the reaction was completed, the reaction solution was returned to room temperature, and slowly poured into methanol (300 mL) cooled to 10°C to precipitate a solid, and stirred for 10 minutes. The obtained solid was collected by filtration, and the obtained solid was further washed with methanol (100 mL) for 10 minutes by stirring twice, and then dried in a vacuum drying oven at 80°C for 6 hours to obtain the target polyimide powder (SPI-3). The imidization rate was 72%.
[0153] <Synthesis Example 9> Polymerization of TC-1 / DA-2, DA-5(50) polyamic acid (PAA-6) DA-2 (2.44g: 10.00mmol), DA-5 (6.85g: 10.00mmol) and NMP (66.0g) were weighed out into a 50mL 4-neck flask equipped with a mechanical stirrer and nitrogen inlet tube, and after stirring for a while to dissolve, TC-1 (4.12g: 18.38mmol) and NMP (10.0g) were added and reacted at 40℃ for 6 hours under a nitrogen atmosphere to obtain a polyamic acid solution (PAA-6) with a solid content of 15% by mass. The viscosity was 380mPa·s and the weight-average molecular weight was approximately 29,600.
[0154] <Synthesis Example 10> Synthesis of TC-1 / DA-2, DA-5(50) Soluble Polyimide (SPI-4) The polyamic acid solution (PAA-6) (30.0 g) obtained in the above Synthesis Example 9 was weighed out into a 100 mL eggplant flask equipped with a nitrogen inlet tube, an air-cooled tube, and a stirrer, and NMP (45.0 g), acetic anhydride (2.42 g: 23.7 mmol), and pyridine (1.25 g: 15.8 mmol) were added. The mixture was stirred at room temperature for 30 minutes under a nitrogen atmosphere, and then stirred at 50 ° C for 3 hours. After the reaction was completed, the reaction solution was returned to room temperature, and slowly poured into methanol (300 mL) cooled to 10 ° C to precipitate a solid, and stirred for 10 minutes. The obtained solid was collected by filtration, and the obtained solid was further washed with methanol (100 mL) for 10 minutes by stirring twice, and then dried in a vacuum drying oven at 80 ° C for 6 hours to obtain the target polyimide powder (SPI-4). The imidization rate was 68%.
[0155] Example 1 Preparation of high anchoring liquid crystal alignment agent (also called strong anchoring liquid crystal alignment agent) AL-1 The polyamic acid solution (PAA-1) (20.0 g) obtained in Synthesis Example 1 above was weighed out into a 50 mL Erlenmeyer flask equipped with a stirrer, and NMP (15.0 g), BCS (15.0 g) and Add-1 (0.15 g) were added, followed by stirring at room temperature for 30 minutes to prepare liquid crystal alignment agent AL-1.
[0156] Example 2 Preparation of high anchoring liquid crystal alignment agent AL-2 The polyamic acid solution (PAA-2) (20.0 g) obtained in Synthesis Example 2 above was weighed out into a 50 mL Erlenmeyer flask equipped with a stirrer, and NMP (8.0 g), BCS (12.0 g) and Add-2 (0.12 g) were added, followed by stirring at room temperature for 30 minutes to prepare liquid crystal alignment agent AL-2.
[0157] Examples 3 to 6 Preparation of Radical-Generating Film-Forming Compositions AL-3 to AL-6 The polyimide powder (SPI-1) (2.0 g) obtained in Synthesis Example 4 above was weighed out into a two-necked eggplant flask equipped with a nitrogen inlet tube and a stirrer, NMP (18.0 g) was added, and the mixture was stirred at 40° C. for 6 hours to dissolve. After confirming that the mixture was completely dissolved, NMP (3.3 g), BCS (10.0 g), and Add-2 (0.10 g) were added, and the mixture was stirred at room temperature for 30 minutes to obtain a radical-generating film-forming composition AL-3. In addition, radical-generating film-forming compositions AL-4 to AL-6 were obtained by preparing the compositions in the same manner as AL-3 above, except that SPI-2 to SPI-4 were used instead of SPI-1, Add-2 was used for SPI-2, and Add-1 was used for SPI-3 and SPI-4, respectively.
[0158] Example 7 Preparation of Radical-Generating Film-Forming Composition AL-7 The strong anchoring liquid crystal alignment agent AL-1 (5.0 g) prepared in Example 1 and AL-3 (5.0 g) prepared in Example 3 were added to a 40 mL sample bottle equipped with a stirrer, and the mixture was stirred at room temperature for 30 minutes to prepare the radical-generating film-forming composition AL-7 of the present invention.
[0159] Example 8 Preparation of Radical-Generating Film-Forming Composition AL-8 The strong anchoring liquid crystal alignment agent AL-1 (5.0 g) prepared in Example 1 and AL-4 (5.0 g) prepared in Example 4 were added to a 40 mL sample bottle equipped with a stirrer, and the mixture was stirred at room temperature for 30 minutes to prepare the radical-generating film-forming composition AL-8 of the present invention.
[0160] Example 9 Preparation of Radical-Generating Film-Forming Composition AL-9 The strong anchoring liquid crystal alignment agent AL-1 (5.0 g) prepared in Example 1 and AL-5 (5.0 g) prepared in Example 5 were added to a 40 mL sample bottle equipped with a stirrer, and the mixture was stirred at room temperature for 30 minutes to prepare the radical-generating film-forming composition AL-9 of the present invention.
[0161] Example 10 Preparation of Radical-Generating Film-Forming Composition AL-10 The strong anchoring liquid crystal alignment agent AL-1 (5.0 g) prepared in Example 1 and AL-6 (5.0 g) prepared in Example 6 were added to a 40 mL sample bottle equipped with a stirrer, and the mixture was stirred at room temperature for 30 minutes to prepare the radical-generating film-forming composition AL-10 of the present invention.
[0162] Example 11 Preparation of Radical-Generating Film-Forming Composition AL-11 The strong anchoring liquid crystal alignment agent AL-2 (5.0 g) prepared in Example 2 and AL-3 (5.0 g) prepared in Example 3 were added to a 40 mL sample bottle equipped with a stirrer, and the mixture was stirred at room temperature for 30 minutes to prepare the radical-generating film-forming composition AL-11 of the present invention.
[0163] Example 12 Preparation of Radical-Generating Film-Forming Composition AL-12 The strong anchoring liquid crystal alignment agent AL-2 (5.0 g) prepared in Example 2 and AL-4 (5.0 g) prepared in Example 4 were added to a 40 mL sample bottle equipped with a stirrer, and the mixture was stirred at room temperature for 30 minutes to prepare the radical-generating film-forming composition AL-12 of the present invention.
[0164] <Preparation of liquid crystal cell> A method for preparing a liquid crystal cell for evaluating the liquid crystal alignment property will be described below.
[0165] First, a substrate with electrodes was prepared. The substrate was a glass substrate with dimensions of 30 mm x 35 mm and a thickness of 0.7 mm. An IZO electrode with a solid pattern was formed on the substrate as the first layer, which constituted the counter electrode. A SiN (silicon nitride) film formed by CVD (chemical vapor deposition) was formed as the second layer on the first layer of the counter electrode. The thickness of the second layer of SiN film was 500 nm, and it functions as an interlayer insulating film. A comb-shaped pixel electrode formed by patterning the IZO film as the third layer was placed on the second layer of SiN film, forming two pixels, the first pixel and the second pixel. The size of each pixel was 10 mm long and approximately 5 mm wide. At this time, the first layer of the counter electrode and the third layer of the pixel electrode were electrically insulated by the action of the second layer of SiN film. The pixel electrode in the third layer has a comb-like shape in which multiple electrode elements, each 3 μm wide and bent at an internal angle of 160° in the center, are arranged in parallel at 6 μm intervals, and each pixel has a first region and a second region separated by a line connecting the bent portions of the multiple electrode elements. Comparing the first and second regions of each pixel, the electrode elements of the pixel electrodes that compose them are formed in different directions. That is, based on the orientation direction of the liquid crystal alignment film described later, the electrode elements of the pixel electrodes in the first region of the pixel are formed to form an angle of +80° (clockwise), and the electrode elements of the pixel electrodes in the second region of the pixel are formed to form an angle of -80° (clockwise). That is, the first and second regions of each pixel are configured so that the directions of rotational movement (in-plane switching) of the liquid crystal induced by the application of a voltage between the pixel electrode and the counter electrode within the substrate plane are opposite to each other. Hereinafter, this will be referred to as the FFS substrate (first substrate).
[0166] Next, the radical-generating film-forming compositions AL-3 to AL12 obtained by the above method, the liquid crystal alignment agent AL-1, and the liquid crystal alignment agent for horizontal alignment SE-6414 (manufactured by Nissan Chemical Co., Ltd.) were filtered through a filter with a pore size of 1.0 μm, and then applied and formed into a film by a spin coating method on the above-prepared first substrate and a glass substrate (hereinafter referred to as the second substrate) as an opposing substrate, which has an ITO film formed on the back surface and has a columnar spacer with a height of 4.0 μm. Next, the substrate was dried on a hot plate at 80° C. for 80 minutes, and then baked at 230° C. for 20 minutes to obtain a coating film with a thickness of 100 nm. The polyimide film on the first substrate side was subjected to an alignment treatment in the direction along the direction of the comb teeth, and the polyimide film on the second substrate side was subjected to an alignment treatment in the direction perpendicular to the comb teeth electrode. The alignment treatment was performed by rubbing for SE-6414, AL-3, AL-4, AL-11, and AL-12, and by photoalignment for AL-1, AL-5, AL-6, AL-7, AL-8, AL-9, and AL-10. The rubbing cloth used was a rayon cloth YA-20R manufactured by Yoshikawa Kako Co., Ltd., and was performed with a roller system of 12 mm, a rotation speed of 700 rpm, a stage feed speed of 30 mm / s, and a pressing pressure of 0.4 mm. For the radical generating film, the rotation speed was 300 rpm, a stage feed speed of 50 mm / s, and a pressing pressure of 0.2 mm. The photoalignment was performed using a UV exposure device manufactured by Ushio Inc., and linearly polarized UV with an extinction ratio of about 26:1 was applied at 50 to 500 mJ / cm2 based on a wavelength of 254 nm. 2 The alignment was performed by irradiating the film with polarized UV light at an irradiation amount between 100 and 200 nm and heating at 230°C for 30 minutes. The alignment conditions giving the best alignment quality were used for comparison.
[0167] Subsequently, for the display elements targeted in the examples, using the above two types of substrates, combinations were made using AL-1 or SE-6414 on the first substrate side and providing radical generation films AL-7, AL-8, AL-9, AL-10, AL-11, AL-12 on the second substrate side. For the display elements used as comparison targets, AL-1 or SE-6414 was used on both substrates, and combinations were made using radical generation films AL-3, AL-4, AL-5, AL-6 on the first substrate side and AL-1 on the second substrate side. They were combined so that their respective alignment directions were parallel, the periphery was sealed leaving a liquid crystal injection port, and an empty cell with a cell gap of approximately 4.0 μm was fabricated. Into this empty cell, a liquid crystal (MLC-3019 manufactured by Merck with 3 mass% of additive IC6 added) was vacuum-injected at room temperature, and then the injection port was sealed to form an anti-parallel alignment liquid crystal cell. The obtained liquid crystal cell constitutes a FFS mode liquid crystal display element. Subsequently, the obtained liquid crystal cell was heat-treated at 120 °C for 10 minutes, and irradiated with UV (UV lamp: FLR40SUV32 / A-1) for 30 minutes using a UV-FL irradiation device manufactured by Toshiba Lighting & Technology Corporation in a state where no voltage was applied to obtain a liquid crystal display element.
[0168] <Evaluation of Liquid Crystal Alignment> Using a polarizing microscope, the polarizer was set to cross Nicol, fixed in a state where the brightness of the liquid crystal cell was minimized, rotated the liquid crystal cell by 1° from there, and observed the alignment state of the liquid crystal. When no unevenness or roughness was observed or when it was very slight, it was evaluated as "good", and when it was clearly observed, it was evaluated as "bad". Also, a photodiode was attached to the same polarizing microscope, connected to an electrometer via a current-voltage conversion amplifier, and the black brightness was measured by monitoring the voltage under the condition where the brightness was minimized under cross Nicol.
[0169] <Measurement of V-T Curve and Evaluation of Driving Threshold Voltage and Maximum Brightness Voltage> A white LED backlight and a luminance meter were set so that the optical axis was aligned, and a liquid crystal cell (liquid crystal display element) with a polarizing plate attached was set between them so that the luminance was minimized. A voltage was applied up to 8V in 1V intervals, and the VT curve was measured by measuring the luminance at each voltage. From the obtained VT curve, the driving threshold voltage and the voltage value at which the luminance is maximized were estimated. In addition, the maximum transmittance was estimated by comparing the maximum transmitted luminance in the VT curve with the transmitted luminance in parallel Nicol mode set to 100% through the liquid crystal cell with no voltage applied.
[0170] <Measurement of response time (Ton, Toff)> Using the same device as in measuring the VT curve above, a luminance meter was connected to an oscilloscope to measure the response speed (Ton) when a voltage was applied that resulted in maximum luminance, and the response speed (Toff) when the voltage was returned to 0 V.
[0171] <Polymer Content> [Table 1]
[0172] <Contents of liquid crystal alignment agent or radical-generating film-forming composition> [Table 2]
[0173] <Contents of the Example Liquid Crystal Cell> The configuration of the liquid crystal cell is shown in Table 3 below. [Table 3]
[0174] <Result> [Table 4]
[0175] Comparative Example 1 is a combination of strong anchoring alignment films for photo-alignment, and Comparative Example 2 and Comparative Example 3 are examples in which the constituent component of the radical-generating film is a single component. Examples 13 to 16 are examples in which a strong anchoring component and a radical-generating component are mixed in the radical-generating film. The black luminance of Examples 13 to 16 is almost the same level as that of the combination of strong anchoring alignment films of Comparative Example 1, and it can be seen that the black luminance is good compared to Comparative Example 2 and Comparative Example 3, the transmittance is also greatly improved, and the delay in response time is suppressed. In particular, it was found that good alignment and black luminance were obtained even in the case of using a radical-generating film component that is not photo-aligned (Example 13 and Example 14), and good weak anchoring characteristics were obtained. On the other hand, Comparative Example 3 has relatively good black luminance and transmittance, but it can also be seen that the black luminance is further improved and the response time is improved by mixing a strong anchoring component (Example 16) rather than a single component.
[0176] Comparative Example 4 is a combination of strong anchoring alignment films for rubbing, and Comparative Examples 5 and 6 are examples of using a radical generating film of a single component that does not undergo photoalignment. In contrast, Examples 17 and 18 are examples of mixing a strong anchoring component for rubbing with a radical generating component. In both Examples 17 and 18, the alignment and black luminance are at the same level as SE-6414, and it can be seen that the transmittance is improved, but the delay in response time is also suppressed.
[0177] Therefore, these verifications demonstrated that by using the radical-generating film-forming composition of the present invention, which is a mixture of a strong anchoring component and a radical-generating component, it is possible to obtain a liquid crystal display element that can achieve both improved transmittance and reduced response time while maintaining good alignment. [Industrial Applicability]
[0178] By using the radical-generating film-forming composition of the present invention, it is possible to provide an in-plane switching liquid crystal display element capable of providing a good black display, high backlight transmittance, and fast response speed. Furthermore, the liquid crystal display element obtained by the method of the present invention is useful as an in-plane switching liquid crystal display element. [Explanation of symbols]
[0179] 1 Liquid crystal display element 2. Interdigital electrode substrate 2a Base material 2b Linear electrode 2c Radical generating membrane 2d base material 2e surface electrode 2f Insulating film 2g linear electrode 2h Radical generating film 3 Liquid crystal composition 4 Opposing substrate 4a Liquid crystal alignment film 4b Base material
Claims
1. A polymer having a structural unit represented by the following formula (1) in its main chain as component (A), and A polymer used as an alignment component of a liquid crystal alignment agent for in-plane switching drive, which is the component (B); Contains The component (B) is at least one selected from a polyimide precursor containing a structural unit represented by the following formula (7) and a polyimide which is an imidized product thereof: The radical-generating film-forming composition, wherein the component (A) and the component (B) each do not contain a vertical alignment group for vertically aligning liquid crystals. 【Chemistry 1】 (In formula (1), A is an organic group that induces radical polymerization and is a group represented by the following formula (3).) 【Chemistry 2】 (In formula (3), the dashed line represents a bond to a benzene ring, and R 6 is a single bond, -CH 2 -, -O-, -COO-, -OCO-, -NHCO-, -CONH-, -NH-, -CH 2 O-, -N(CH 3 )-,-CON(CH 3 )- or -N(CH 3 ) CO-, R 7 represents a single bond, or an unsubstituted or fluorine-substituted alkylene group having 1 to 20 carbon atoms, 2 -or-CF 2 One or more - may be independently replaced by a group selected from -CH=CH-, a divalent carbocyclic ring, and a divalent heterocyclic ring, and may further be replaced by any of the following groups, i.e., -O-, -COO-, -OCO-, -NHCO-, -CONH-, or -NH-, provided that they are not adjacent to each other: R 8 represents an organic group capable of inducing radical polymerization, represented by a formula selected from the formulae [X-1] to [X-18], [W], [Y], and [Z]; 【Chemistry 3】 In formulas [X-1] to [X-18], * represents R 7 indicates the bonding site with S 1 and S 2 each independently represents -O-, -NR-, or -S-, R represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 4 carbon atoms, 【Chemistry 4】 In the formulas [W], [Y], and [Z], * represents R 7 represents the bonding site with 3 is a single bond, -O-, -S-, -COO-, -OCO-, -NHCO-, -CONH-, -NH-, -CH 2 O-, -N(CH 3 )-,-CON(CH 3 )- or -N(CH 3 )CO-, Ar represents an aromatic hydrocarbon group selected from the group consisting of phenylene, naphthylene, and biphenylylene, which may have an organic group and / or a halogen atom as a substituent, R 9 and R 10 are each independently an alkyl group, an alkoxy group, a benzyl group, or a phenethyl group having 1 to 10 carbon atoms. In the case of an alkyl group or an alkoxy group, R 9 and R 10 may form a ring, Q represents any one of the following structures: 【Chemistry 5】 In the formula, R 11 Ha-CH 2 represents -, -NR-, -O-, or -S-, where R represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and * represents a bond; R 12 represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms. 【Chemistry 6】 (In formula (7), X 2 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y 2 is a divalent organic group derived from a diamine not containing the structure of formula (1), R 5 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and R 6 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.)
2. 2. The radical-generating film-forming composition according to claim 1, wherein the polymer of component (A) is at least one polymer selected from the group consisting of a polyimide precursor obtained by using a diamine component containing a diamine containing an organic group that induces radical polymerization, a polyimide, a polyurea, and a polyamide.
3. 3. The radical-generating film-forming composition according to claim 2, wherein the diamine containing an organic group capable of inducing radical polymerization is a diamine represented by the following formula (2): 【Chemistry 7】 (In formula (2), A 1 and A 2 each represents a hydrogen atom or an organic group capable of inducing radical polymerization, 1 and A 2 At least one of represents an organic group that induces radical polymerization, E is a single bond, —O—, —C(CH 3 ) 2 -, -NH-, -CO-, -NHCO-, -COO-, -(CH 2 ) m -, -SO 2 -, or any combination thereof, and m is an integer of 1 to 8. p represents an integer of 0 to 2. When p is 2, a plurality of A 2 Each independently has the same definition as above. When p is 0, A 1 consists of organic groups that induce radical polymerization.
4. A radical-generating film obtained by using the radical-generating film-forming composition according to any one of claims 1 to 3.
5. A step of preparing a first substrate having a liquid crystal alignment film and a second substrate having the radical generating film according to claim 4; preparing a cell such that a radical generating film on the second substrate faces the first substrate; and A method for manufacturing a horizontal electric field liquid crystal cell, comprising a step of filling a liquid crystal composition containing liquid crystal and a radically polymerizable compound between the first substrate and the second substrate, wherein one of the first substrate and the second substrate is a comb electrode substrate and the other is an opposing substrate.
6. 6. The method for producing an in-plane switching liquid crystal cell according to claim 5, wherein the first substrate is a substrate coated with a liquid crystal alignment film having uniaxial alignment.
7. 7. The method for producing an in-plane switching liquid crystal cell according to claim 6, wherein the liquid crystal alignment film having uniaxial alignment is a liquid crystal alignment film for horizontal alignment.
8. 8. The method for producing an in-plane switching liquid crystal cell according to claim 5, wherein the comb electrode substrate is an IPS substrate or an FFS substrate.
Citation Information
Patent Citations
Method of aligning liquid crystal having no anchoring in plane and non-contact liquid crystal aligning method using the same, and liquid crystal display device
JP2013231757A
Optical aligning materials
JP2014532104A
Liquid crystal aligning agent for photo-alignment, liquid crystal alignment film and liquid crystal display element using the same
JP2019211777A
Zero plane anchoring liquid crystal alignment method and its liquid crystal device
JP4053530B2
Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element
WO2018047872A1